Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2022)
A dataset containing 1849172166 species occurrences available in GBIF matching the query: { "BasisOfRecord" : [ "is Human Observation" ] } The dataset includes 1849172166 records from 14740 constituent datasets: 18 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Especies observadas en Mercedes (Unterkofler, octubre 1999). 58 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du/de la naturaliste Williamson Thomas provenant de la base de donnée du SINP Île-de-France CETTIA. 445 records from Oceanic Society's Marine Mammal Sightings in Belize 1992 - 2011. 108 records from MIRC NAVFAC Incidental Sightings - Aerial 1965-2014. 158 records from Waldstück Bremerhagen LK Bio Kl. 12. 15 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Inventaire des mammifères du Parc de la Haute-Île (93). 52 records from Distribution of Aureoboletus projectellus in Europe. 13230 records from Suivi des oiseaux de passage : programme FLASH - Programme FLASH : Répartition Pigeon ramier 2012 - 2016 Coordonnées GPS Lambert 93. 235 records from Estimación de la densidad poblacional y dieta del lince (Lynx rufus) Sierra Seri, Sonora y Janos, Chihuahua. 2154 records from DBG Physaria bellii Demographic Monitoring. 1716750 records from Dragonfly records from the British Dragonfly Society Recording Scheme. 4 records from (Table 1) PBDE and BDE congener concentration in adipose tissue of East Greenland polar bears collected 1999-2001. 2706 records from Plan de gestion de la Réserve Naturelle Régionale de la Massonne - Inventaire de données. 118 records from Frestoy-Vaux, Mortemer, Rollot - 60/80 - Frestoy-Vaux/Mortemer/Rollot - Flore. 50 records from Inventario de vertebrados nativos en las islas Guadalupe, San Benito, Natividad, Asunción, San Roque, Isabel, Marietas, Socorro, Banco Chinchorro y Arrecife Alacranes (Crustáceos). 16 records from Size fractioned abundances and carbon biomasses of heterotrophic protists at station NIOP-B1_276-1. 12273 records from Invasive Plant Atlas of the MidSouth (IPAMS). 14 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/091-4. 71 records from Invasive plants in Luronium natans habitats in Flanders, Belgium. 1 records from Happywhale - Indian Ocean bottlenose dolphin in Indian Ocean. 74 records from Biodiversity of the Desna river valley and its tributaries. 371 records from Bannwald Burghauser Forst. 942 records from Bibliographie de la faune, la flore et la fonge de France métropolitaine et outre-mer - Bulletin du Muséum d'Histoire Naturelle [1895- ]. 6 records from Sarcodine counts and carbon biomass at station TT007_8-CTD99. 7 records from The publication of primary biological events in the international GBIF (Global Biodiversity Information Facility) network: A case study with a small dataset of field collected occurrence samples of Buriti palms (Mauritia flexuosa).. 50 records from Reptiles de la Ecoreserva ASA (Meta, Acacías) - Proyecto FIBRAS. 25471 records from SEWBReC Bees, Wasps and Ants (South East Wales). 333 records from Données du Comité Départemental de Protection de la Nature et de l'Environnement de Loir-et-Cher (CDPNE) - Données 2016 Pélobate brun Comité Départemental de Protection de la Nature et de l'Environnement. 5720 records from Fitoplancton de la provincia oceánica del mar Caribe colombiano. Diez años de historia. 3 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station JUNE-1998-IR50. 8 records from HRC Koa Kai Marine Species Monitoring Vessel Surveys November 2010. 17484 records from Fish of the Recherche Archipelago , Western Australia (2002). 89 records from Great British Bee Count 2016 - Stage 2 (records verified from photo). 667 records from Antarctic Krill occurrence data from Discovery expeditions. 1140 records from Total foraminifera counts of multinet M33/1_MSN1029. 19 records from Chronicle of Nature - Phenology of Insects of National Park Bashkirija. 833 records from Plant species from the sacred and community forests of Mono departement. 480819 records from KTP Ring Data. 263 records from Observations naturalistes indépendantes d'origine privée partagées sur la base de données Kollect Nouvelle-Aquitaine - Observations faunistiques de Florent HERVOUET. 151 records from Monocotiledóneas del cerro Tacarcuna-Chocó, en el marco del proyecto Colombia BIO 2017. 87 records from Artenvielfalt des "Grünen Klassenzimmers". 69 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Vireonidae. 11 records from Données de Shell Exploration and Production France - Données d'observation opportunistes collectées durant la campagne de prélèvements sédimentaires SHELL/CREOCEAN en Guyane française en 2013. Shell Exploration and Production France. 1 records from Synthèse de la Répartition des populations de cerf élaphe en 2000 (réseau Ongulés sauvages ONCFS-FNC-FDC). 35 records from Zoocenosis of the mole burrows in the forest zone of Western Siberia. 1422 records from Australian Institute of Marine Science (AIMS) - Lizard Island Reef Biodiversity Expedition, Queensland, Australia (2008 - 2009). 13230 records from Suivi des oiseaux de passage : programme FLASH - Programme FLASH : Répartition Pluvier doré 2012 - 2016 Coordonnées GPS Lambert 93. 23 records from Morphologische Daten von Natrix. 167 records from AMAPPS Southeast Aerial Cruise Fall 2016. 8352 records from Inventario florístico y entomofaunístico en tres objetos de conservación ecosistémicos en las zonas núcleo de las reservas estatales de Balam-kú y Balam-kin, Campeche (Plantas). 115 records from Plan de gestion 2017 - 2021 du site des Landes humides de Mazerolles (64) mené par le CEN Nouvelle-Aquitaine - Observations d'odonates (imagos) réalisées par le CEN Aquitaine selon le protocole STELI. 26524 records from Plasm bearing foraminifera counts during METEOR cruise M36/5. 12 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/041-2. 141 records from Inventaire biodiversité du site Pierre Fabre d'Aignan. 90 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du/de la naturaliste Le baron Gaetan provenant de la base de donnée du SINP Île-de-France CETTIA. 598 records from Caracterización biológica de la ventana de biodiversidad Montes de María, Municipio de Colosó, Sucre, Colombia. 95 records from BIRDRACE accipiter hardcore birding. 19769 records from Inventaire de la flore des Pyrénées-Atlantiques (hors massif pyrénéen) - Inventaire de la flore des Pyrénées-Atlantiques 2017 - Littoral. 71 records from Occurrence of mammalia relicts at site Spitzbubenhöhle. 324 records from Marine Mammal Observation - Total E&P Angola 2006-2011. 684 records from Plasm bearing foraminifera counts of multinet M12/3_MSN562. 13 records from Projet de parc éolien sur la commune d'Envronville - Données faune terrestre. 133176 records from Happywhale - Humpback Whale in North Pacific Ocean. 5 records from Projet d'extension de carrière et de mise en place d'une unité de concassage de produits minéraux - Pierrefonds - Saint-Pierre (974) - Inventaires des Reptiles. 24 records from Inventaires et suivis sites "Espaces Naturels Sensibles" gérés par le Conseil Départemental des Landes - Inventaire "Espaces Naturels Sensibles" site de La Beute (Tosse). 11125 records from Collections of Bioclass, school #179, Moscow. 11080 records from BLM CETAP AIR Sightings. 51 records from Inventaires et suivis sites "Espaces Naturels Sensibles" gérés par le Conseil Départemental des Landes - Inventaires "Espaces Naturels Sensibles" du Luy (Saugnac-et-Cambran). 229 records from Distribución y estructura poblacional de la tortuga de Berlandier, (Gopherus [=Xerobates] berlandieri) en México. 336 records from Aves del cerro Tapartó, Santa Cecilia - Risaralda. 2020. 21 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT012_3-CTD4. 912 records from Plasm bearing foraminifera counts of multinet M36/6_MSN1197. 26 records from Hongos endófitos asociados a ecosistemas de boques tropicales en Cali. 24 records from Réserves Naturelles de France (RNF) - RNF - Données de la Réserve Naturelle du Marais de Lavours. 54550 records from Digital Aerial Baseline Survey of Marine Wildlife in Support of Offshore Wind Energy - OPA 2016. 14520 records from Inventario de flora, avifauna, mamíferos, mariposas y peces realizado en el sector de Puerto Abeja y durante la expedición científica en la ventana Mesay en el sector sur del Parque Nacional Natural Serranía de Chiribiquete. 42 records from Inventaire des Octocoralliaires des fonds sédimentaires de la région niçoise. 1477 records from Inventaire des espèces végétales productives dans les Systèmes Agro-forestiers aux alentours de la Forêt classée de Ziama en Guinée Forestière (BID-AF2015-0066-REG). 3 records from BioAcoustica: Wildlife Sounds Database. 392 records from Bat species occurrences in Nyungwe National Park, Rwanda. 68 records from (Table 2) Occurrence of upper Maestrichtian to Eocene benthic foraminifers in ODP Hole 121-753A. 11840 records from Coral Reef Evaluation and Monitoring Project Florida Keys 2015. 36 records from (Table 1) CTD data, mean spring and annual temperatures and salinities from World Ocean Atlas (WOA, 2001), and Mg/Ca data, sampled with a multinet at station 74 and 81 from POSEIDON cruise 334. 47 records from Etude avifaunistique de la LPO Limousin sur les landes haut-viennoises - Inventaire et suivi Avifaune de la lande de Massaloux. 1627 records from TransForest - vegetation, lichen and fungi data 2016. 4 records from Plan de gestion 2016 - 2020 du site des Coteaux de Saint-Victor et Montagrier (24) mené par le CEN Nouvelle-Aquitaine - Observations faunistiques fortuites réalisées par le CEN Nouvelle-Aquitaine. 2845 records from Pat Livermore's Fungus Records 1976 - 2000. 180 records from Microzooplankton abundance measured on water bottle samples at station PS65/466-2. 201 records from Biodiversity of springs and rock seepages 2003. 146 records from Registros de la vegetación presente en la Cienaga de Beté, Municipio del Medio Atrato, Chocó - 2018. 36323 records from Biowide Species data. 11 records from Elaboration du DOCOB du site Natura 2000 ‘Zones humides de Moliets, la Prade et Moïsan’ (FR7200717) - Inventaire et regroupement de données Natura 2000. 18 records from Observations naturalistes indépendantes d'origine privée partagées sur la base de données Kollect Nouvelle-Aquitaine - Observations faunistiques de Vincent DUPRAT. 816 records from Línea base general de peces para el valle medio del Magdalena - VMM. 210 records from Condamine Alliance. 181 records from Inventory of natural and agroforestry stands characterized by Xylopia aethiopica (Dunal) A. Rich. (south-Benin). 521 records from Schanzenanlage Bergham. 4 records from Distribution of Quinqueloculina sp. in sediment core 13200-025. 3622 records from Mesures compensatoires sur des projets de Collectivités territoriales - Données CEN L-R Compensation collectivités. 1140 records from Total foraminifera counts of multinet POS231/3_MSN1332. 275 records from Large protozoan and small metazoan abundance measured on concentrated water bottle samples at station PS65/587-16. 748 records from AMAPPS Northeast Aerial Cruise Summer 2010. 547 records from Données du Parc national de la Réunion - Données du Geckos vert des Hauts (Phesulma borbonica) du Parc national de La Réunion. 160 records from AVJNF: Søholt Storskov, amphibian survey. 18 records from Naturtag. 45 records from données espèces - Expertise IPE 63. 3604 records from Phytoplankton abundance and species composition in the Tyrrhenian Sea in November 1981. 41 records from HRC CRC Small Vessel-Based Monitoring Surveys July 2006. 42 records from Inventaire des oiseaux pour le projet de parc solaire de Ribeyret. 163994 records from Inventaire des oiseaux nicheurs de France métropolitaine 2009-2012 - Oiseaux nicheurs de France métropolitaine 2009-2012 - Nidification probable. 444 records from Marsabit Ecosystem Inventory Surveys 2014. 4 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de BLANC Josselyne. 912 records from Plasm bearing foraminifera counts from M35/1_MSN1069. 1480 records from Monitoring of colonial waterfowl species (2013-2014). 208 records from Abundances and biological traits of the juveniles trout sampled in the survey of trout abundance Indices (VIGITRUITE®) in the Bresle river (France). 69 records from Siphonaptera and Phthiraptera Recording Scheme - records verified via iRecord. 1089 records from (Table 1) Range chart for planktonic foraminifers from ODP Hole 111-667A. 57 records from Schulgelände SGD/Viersen. 1533 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du/de la naturaliste ARNABOLDI Frédéric provenant de la base de donnée du SINP Île-de-France CETTIA. 774 records from Biodiversidad ictica de la Isla Cayo Serranilla Expedición Seaflower 2017 proyecto Colombia BIO. 59 records from Visual and genetic surveys for odontocete cetaceans in American Samoa 2003-06. 15 records from Monitoreo de Murciélagos en la Etapa de Ejecución de las Obras de Ampliación del EPF Floreña, Yopal, Casanare. 30 records from Phytoplankton abundance at station Casma_2003-01-30_2, Casma, Peru. 3206 records from Parc éolien la Croix de la Mérotte - Données Biodiversité Etude d'impact parc éolien Croix de la Mérotte. 45 records from Plan de gestion 2015 - 2019 du site du Coteau de Monco (33) mené par le CEN Aquitaine - Observations faunistiques fortuites réalisées par le CEN Aquitaine. 1 records from Registro de Chromolaena tacotana asociado al proyecto: Relación estructura-actividad anti-cáncer de flavonoides sobre líneas celulares cancerosas. 136 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Inventaire faunistique de l'ENS des Parc des berges de Seine. 11198 records from Overvåking av åpen grunnlendt kalkmark i Oslofjordområdet. 958 records from Collection de longicornes et autres coléoptères saproxyliques de Lionel Valladares. 3435 records from Benthos Chirnov Basin 1986 and 2002. 912 records from Plasm bearing foraminifera counts of multinet POS247/2_MSN1379. 1011 records from SCANS II cetacean sightings on primary platform of vessel surveys 2005. 78 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de Monsieur LAFAGE Denis. 192 records from Planktic foraminifera counts at CTD station M39/4_402CTD-55. 1 records from Molche in Ruschwedel. 708 records from EDP Baixo Sabor: Herpetology – Baseline Studies [2009]. 1020 records from Suivi des oiseaux de passage : programme ACT - Programme ACT : Répartition Pie bavarde 2010 - 2014 Coordonnées GPS Lambert 93. 68 records from Centrale Hydroélectrique de Port à l'Anglais. 9115 records from Données orthoptères en Auvergne, observations d'Emmanuel Boitier. - Données d'observations d'orthoptères en Auvergne, d'Emmanuel Boitier, de 1998 à 2015.. 228 records from Abundance and habitat of echinoderms collected during the Bangor-Watamu Expedition in 1969. 971 records from Vascular Plants from Praia da Vitória (Terceira, Azores, Portugal). 2441 records from Análisis de las relaciones entre las diversidades alfa, beta y gamma a distintos niveles de escala espacial: Procesos históricos y ecológicos que intervienen. V Etapa. 158 records from Herpetofauna and other animals registered within Rzhyshchiv city amalgamated territorieal community (CATC) (Kyiv region) in 2021. 760 records from Plasm bearing foraminifera counts of multinet M21/1_MSN620. 2 records from Plan de gestion 2015 - 2020 du site du site des zones humides du Mondarrain et de l'Artzamendi (64) mené par le CEN Nouvelle-Aquitaine - Observations faunistiques fortuites réalisées par le CEN Nouvelle-Aquitaine. 726 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes d'Arnaud LE NEVÉ. 23798 records from Swan Coastal Plain Survey. 5786 records from Biomass and mortmass of woody vegetation in metal-contaminated areas (Southern Urals, Russia). 2147 records from University of Amsterdam (NL) - Páramo Vegetation Research, National Natural Park El Cocuy, Colombia. 950 records from Total foraminifera counts of multinet M21/4_MSN704. 164 records from Harpacticoid copepods in tropical seagrass beds of Gazi Bay (Kenya) and Mbweni (Zanzibar) sampled in July and August 1996. 184 records from Plan de gestion 2017 - 2021 du site des Coteaux du Légal (24) mené par le CEN Aquitaine - Observations ornithologiques (Indice Ponctuel d'Abondance) réalisées par Vya Natura (étude de l'avifaune nicheuse). 99 records from Mise à jour Zones naturelles d'intérêt écologique, faunistique et floristique (ZNIEFF) - Données CEN M-P ZNIEFF. 8 records from Observations naturalistes indépendantes d'origine privée partagées sur la base de données Kollect Nouvelle-Aquitaine - Observations faunistiques de Thorsen ANDRONIK. 26224 records from Zomerganzen - Summering geese management and population counts in Flanders, Belgium. 204 records from Happywhale - Leopard seal in South Atlantic Ocean. 266 records from Abundance of broken diatom frustules measured on water bottle samples at station PS58/088-4. 28 records from Projet de carrière - Ravine du Trou - Saint-Leu (974) - Inventaires des Reptiles. 717 records from Redland City Council Citizen Science Portal. 15 records from Hessen-GEO-Tag am Schlossberg von Homberg/Efze. 371 records from IOV-UDO-ZOOPLANCTON-PLAYA COLORADA. 374 records from HBRG Invasive Non-native Plants Dataset. 180 records from Caracterización de algas y comunidad íctica de la Isla Cayo Serrana durante la Expedición Seaflower 2016 - Proyecto Colombia BIO. 61681 records from North East Scotland Terrestrial Mammals 1900-2017 (excluding squirrels, wild cats and marine mammals). 470 records from 59 - Beau Gui Avifaune. 253 records from EDP Foz-Tua: Riparian Birds (point counts) Ecological Monitoring Program [2011]. 31 records from Regroupement d'études et inventaires - Suivi gravières GSM. 163 records from Steinbruch Mainz-Weisenau, 3. Jahr. 120 records from BIRDRACE The early birds. 2147 records from Regroupement d'études et d'inventaires - Données odonates collectées par le CEN Aquitaine entre 1995 et 2015. 229 records from Queen Charlotte Sound / Tōtaranui and Tory Channel / Kura Te Au (HS51) Hydrographic Survey Marine Mammal Observations. 1289 records from RECORD Orthoptera Data. 50076 records from DFO Pacific Outside South Hard Bottom Longline Surveys. 70 records from ONCFS Réseau Ours brun - Ours 2010 présence Occasionnelle Mailles 10km LAEA Réseau Ours brun ONCFS. 718 records from Bird species occurrences recorded from selected sites in mid Tana River Basin, Kenya. 368 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du naturaliste PROVOST romain provenant de la base de donnée du SINP Île-de-France CETTIA. 93 records from Wildlife Sightings in the City of Logan. 1151 records from MBON POLE TO POLE: ROCKY SHORE BIODIVERSITY OF ARRAIAL DO CABO - BRAZIL. 115 records from Antarctic Pycnogonids II. 32 records from Schulgelände Kranich-Gymnasium (Salzgitter). 7 records from Oberservation of birds at station PS14/143 along 49° West. 469 records from Suivi de l'expansion du Frelon asiatique (Vespa velutina) : données espèces non cibles piégées. 541 records from Caracterización de Fauna del Banco de Hábitat del Bosque Seco Tropical Antioquia de Terrasos. 173 records from Transfert de fichier de données naturalistes d'observateurs indépendants à l'Observatoire FAUNA - Données naturalistes de Julien PIOLAIN. 1555 records from Herpetofauna de la región marina prioritaria Corredor Puerto Madero, Chiapas, México. 6979 records from Upper Silesian Museum, Bird Observations. 86 records from Fliegenhaupt Marksuhl. 596 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de Quentin ROME. 2199 records from Back from the Brink vascular plant species abundance and distribution for Great Britain for the period 2002-2009. 98 records from Occurrence of mammalia relicts at site Rejtek 1. 133 records from Ecomorphology of the mangrove oyster Crassostrea cucullata in a mangrove swamp in Gazi (Kenya) in May 1991. 269 records from SEWBReC Springtails and allies (South East Wales). 101 records from Animation technique des sites Natura 2000 ‘Barthes de l'Adour’ - Suivi Pics 2012 - Site Natura 2000 des Barthes de l'Adour. 62 records from Polychaeta and Oligochaeta of the Auckland and Campbell Islands, New Zealand, 1941-1945. 64 records from Bats of northeastern Vietnam. 1519 records from IBF Monitoring of Fungi. 130 records from Artenvielfalt auf dem Schulgelände. 103 records from Notice de gestion 2014 - 2018 de la bande de servitude de l'artère Girland (40) de Teréga mené par le CEN Aquitaine - Observations faunistiques (inventaire) réalisées par le CEN Aquitaine. 1809 records from BenthosChukchiFN762_1976_Falk5. 20 records from Projet de parc solaire Figanieres - Reptiles - inventaire non protocolé. 117 records from BD de la plateforme partagée pour la diffusion des données naturalistes de Haute-Normandie - Programme de valorisation des zones humides chassées - volet Amphibiens. 3018 records from Caracterización de flora, edafofauna epígea, anfibios y aves del Complejo de Páramos Pisba, Boyacá. 27 records from Caracterización floristica del Alto del Buey, Bahia Solano - Chocó. 165 records from Diversidad de anfibios en tres coberturas vegetales y su relación con actividades antrópicas (amenazas) presentes en el Parque Nacional Natural Tatamá y su área de influencia. 11 records from (Table 2) Population density and zoobenthos biomass in bottom communities of the Novosibirsk Polynya in September 2008. 22192 records from Transfert de fichier de données naturalistes d'observateurs indépendants à l'Observatoire FAUNA - Données naturalistes de Alain Noël. 484 records from Service National d'Observation CORAIL - Agencement temporel des populations et des peuplements d'invertébrés benthiques. 330 records from Large protozoan and small metazoan abundance measured on concentrated water bottle samples at station PS65/593-18. 69 records from BIRDRACE Pfeifenten. 73 records from Données 2017 de l'Observatoire de la Biodiversité des Forêts. 23449 records from Port Phillip Bay Environmental Study Data 1992-1996 - benthic records. 1575 records from Hermatypic Corals of Western Australia. 147 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données de la naturaliste Laurence Beauchamp. 154 records from Ferme Eolienne de la Région de Guise - Données écologiques de la ferme éolienne de Guise. 236 records from Knechtweide (Kohlfurth). 164 records from Ladybirds of Ireland. 797 records from DOSSIER DE DEMANDE DE RENOUVELLEMENT D’AUTORISATION D’EXPLOITATION DE CARRIERE, Communes de Saint-Andéol-le-Château et Givors (69) - Flore St Andéol-1. 13226 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de Bruno OGER. 358 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du Syndicat de la Vallée de l'Orge Aval (SIVOA). 89 records from Meniscus Midges (Dixidae) of Ireland. 148 records from Plan de gestion 2016 - 2020 du site du coteau de Pinel (47) mené par le CEN Nouvelle-Aquitaine - Observations faunistiques (inventaire) réalisées par le CEN Aquitaine. 1285 records from Service National d'Observation CORAIL - Suivi des aires marines protégées de Moorea - Invertébrés benthiques. 15 records from Suivi de la colonie de Pipistrelles de la Petite Ceinture à Paris. 20 records from Riedkanal Bötzingen. 11 records from Liaison autoroutière concédée entre Machilly et Thonon les Bains et suppression des passages à niveau N° 65 et 66 à Perrignier Haute-Savoie - Reptiles - Inventaire non standardisé - LPO74. 54 records from Aves marinas del atolón Albuquerque durante la Expedición Seaflower 2018 - Proyecto Colombia BIO. 1024 records from Suivi des oiseaux de passage : programme ACT - Programme ACT : Répartition Merle noir 2001 - 2005 Coordonnées GPS Lambert 93. 686 records from Expediciones en biodiversidad alrededor del Cacao en el marco del proyecto Colombia Bio. 495 records from Large protozoan and small metazoan abundance measured on concentrated water bottle samples at station PS65/591-11. 171 records from Alien Species in Poland - Animals. 1305 records from Occurrence database of native plants and animals of south-central Chile. 83 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du/de la naturaliste Swoszowski Florie provenant de la base de donnée du SINP Île-de-France CETTIA. 52 records from Occurrence of mammalia relicts at site Pestera Bursucilor. 79623 records from Swiss National Bat Databank: Regional Coordination Western Switzerland (CCO). 6192 records from NE Scotland fish records 1800-2010. 259 records from Base BOMBINA du Parc Naturel régional Lorraine - Natura 2000 Parc naturel régional de Lorraine. 144337 records from Données de l'AFB acquises selon le protocole de pêche complète à un ou plusieurs passages. 2271 records from Happywhale - Humpback Whale in Indian Ocean. 130 records from Réseau Loup - Lynx ONCFS - Réseau Loup-Lynx : Répartition communale Régulière du Loup en 2008. 184 records from Foraminifera species abundances from tow TT011_7-MOC66. 58372 records from Fichier communal des ongulés. 93 records from BIRDRACE Punkbirder Helgoland. 510 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/041-2. 5 records from Sächsische Schweiz (Pfaffenstein). 344 records from Conservación de la tortuga caguama del Pacífico (Caretta caretta): protección dentro del hábitat crítico de alimentación y desarrollo en Baja California Sur. 809 records from Especies vegetales asociadas a intervenciones de micrositios en la Reserva Forestal Thomas van der Hammen. 3 records from Happywhale - Green Sea Turtle in North Pacific Ocean. 2194 records from Modelos predictivos de distribución geográfica para Spizella wortheni, Cynomys mexicanus, Vulpes macrotis zinseri y Taxidea taxus berlandieri. 9 records from Records of pine martens from SNH casework reports and licence applications, 2005 - 2016. 7527 records from Fauna y flora en áreas con cultivos de palma de aceite en el norte y oriente de Colombia. 2997 records from MMS Seabird Ecology Study 1985. 71 records from Bringing Reedbeds to Life Water Vole and Mink Survey of five key reedbed sites in England in 2009, 2010. 1424 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du/de la naturaliste Chevreau David provenant de la base de donnée du SINP Île-de-France CETTIA. 18 records from Cyanobacteria, phototrophic and heterotrophic pico-nanoplankton at station TT007_10-CTD124. 2099 records from SILENE-FAUNE-PACA - Communauté_de_communes_Asse_Bléone_Verdon_2017_12_18. 9 records from Occurrence of mammalia relicts at site Climauti II. 315 records from Phytoplankton abundance measured on water bottle samples at station PS65/545-1. 192 records from PeECE II - Pelagic Ecosystem CO2 Enrichment Study, Raunefjord, Bergen, Norway. 266 records from Abundance of broken diatom frustules measured on water bottle samples at station PS58/092-3. 42 records from ONCFS Réseau Ours brun - Ours 2006 présence Occasionnelle Mailles 10km LAEA Réseau Ours brun ONCFS. 12 records from Art´n Vielfalt im Kinderwald. 135 records from Waldi-Weiher. 50 records from Herpetofauna de la expedición Pisba - Proyecto Boyacá BIO UPTC. 492 records from Invasive Non-Native Species, Outer Hebrides. 251819 records from Phase 2 Lowland Grassland Survey of Wales. 459 records from Gewann Krampf (Heilbronn). 225 records from AFTT JAX Aerial Survey -Left side- 2014. 389 records from Amphibian and Reptilian (KIEE-AR). 74 records from Naturschutzgebiet Lippeaue (Marl) - Pfadis in Sickingmühle. 50 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données de NICOLAS Vincent (SAPROX). 6 records from Plan de gestion 2016 - 2020 du site des Coteaux de Saint-Victor et Montagrier (24) mené par le CEN Nouvelle-Aquitaine - Observations faunistiques fortuites réalisées par le CEN Aquitaine. 3836 records from Projet de parc éolien en mer des îles d'Yeu et de Noirmoutier - demande de dérogation espèces protégées - Oiseaux PT - Inventaire non protocolé. 607 records from Inventory of Bassila forest (North-Benin). 18 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT007_1-CTD8. 493 records from Fauna and population of oribatid mites (Acari, Oribatida) in the vicinity of Kosogorsky metal works (Tula Region, Russia). 1029 records from Circumpolar Seabird Monitoring Plan. 84 records from Projet Vianne : construction et exploitation de canalisations de transport de gaz naturel sur les communes de Thouars-sur-Garonne, Feugarolles, Vianne, Lavardac et Nérac (Lot-et-Garonne) - Données faune-flore recueillies dans le cadre de l'étude d'impact. 18 records from Catch related distribution of Appendicularia at station M9_C near the Great Meteor Bank, Northeast Atlantic (Table 8). 6 records from Enquête sur 3 mammifères protégés : le Muscardin, le Campagnol amphibie et la Crossope aquatique - Données mammifères Phase 2 récoltées par LPO France. 330 records from (Table 2) Distribution of calcareous nannoplankton in selected samples of ODP Site 112-679. 100 records from Phytoplankton abundance measured on water bottle samples during Jan Mayen cruise JM2. 38 records from Phytoplankton counted on two fractions of surface sediment samples from stations B-5 to B-47. 1371802 records from CLICNAT- Base de données naturaliste picarde - CLICNAT Base de données naturaliste picarde gérée par Picardie Nature. 237179 records from Leicestershire and Rutland Environmental Records Centre records 2015-2019. 413272 records from DATAVES. 23 records from Herpetofauna asociada a la cuenca del río Quito - Chocó, 2014. 979 records from DATABASE OF FINDS OF RARE LICHEN SPECIES Lobaria pulmonaria IN RUSSIA. 8 records from Microplankton abundance in the euphotic zone of the Cretan Sea at Station JULY-1994-D2. 2436 records from Diet results from Adelie penguins at Bechervaise Island and Whitney Point, 2012/13. 8952 records from Gestion de sites - Données ANA - CEN Ariège sur la gestion conservatoire (occurences de taxons). 372 records from Composición y estructura de la ornitofauna de la reserva de la biósfera Pantanos de Centla. 156 records from SNH Invertebrate Site Condition Monitoring 2013/14: Earlshall Muir SSSI. 1016 records from Suivi des oiseaux de passage : programme ACT - Programme ACT : Répartition Tourterelle turque 2012 - 2016 Coordonnées GPS Lambert 93. 6 records from (Table 1) Nesting characteristics of greater snow geese (Chen caerulescens atlanticus) on Bylot Island between 1995-2005. 36 records from Regroupement d'études et inventaires de la Réserve Naturelle de la Tourbière des Dauges - FR3600144 - Ensemble des données bibliographiques. 2 records from Nano and microzooplankton abundance and biomass at station NBP97-01-01-10. 4 records from Determinación de la clase Reptilia presente en el corregimiento de Juanchaco, Valle del Cauca, Colombia para el mes de Septiembre de 2017. 108 records from (Table 2) Species density and composition of an inshore and offshore station in Kongsfjord, Svalbard. 300 records from Planktic foraminifera counts at CTD station PS55/078-1. 700 records from Distribution of nanoplankton at trap WR2. 79 records from Birdrace-Bielefinken-Bielefeld. 9657 records from SILENE-FAUNE-PACA - Ecosphère_2017_12_18. 94 records from Müritz-Nationalpark. 642 records from Flora vascular y no vascular:expedición El Consuelo - Proyecto Boyacá BIO UPTC. 162 records from (Table 2.2.1.1) Abundance of sympagic meiofauna of sea-ice core IO-2. 880 records from Phytoplankton abundance in surface water in October 1997, Pisco, Peru. 378 records from Rock ptarmigan (Lagopus muta) radio telemetry in Lierne, Norway. 146 records from Birdrace-Wannacks_Topti(c)ker-Lübeck. 141813 records from Fermanagh Flora. 270 records from Wald am Schloss Wittgenstein Bad Laasphe. 4512 records from Actualización y enriquecimiento de las bases de datos del proyecto de evaluación y análisis geográfico de la diversidad faunística de Chiapas. 3529 records from A dataset from bottom trawl survey around Taiwan. 14666 records from Tachinid Recording Scheme - Tachinid fly records verified via iRecord. 4 records from Pheronema on the mid-Atlantic Ridge, data from NRCan. 794 records from Isle of Wight non-native invasive species. 24 records from Phytoplankton abundance in surface water in 2003, Ancon, Peru. 5299 records from Conservación y monitoreo de anfibios en riesgo de extinción en Chiapas. 7027 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de LUPOLI Roland. 68 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du/de la naturaliste JOSSERAND oriane provenant de la base de donnée du SINP Île-de-France CETTIA. 581 records from Floristic records in the Moscow and Novgorod regions. 58 records from Phytoplankton abundance at station Sechin_2003-10-03_2, Casma, Peru. 46 records from Weber State University Herbarium. 800 records from Inventarios de la biodiversidad en el piedemonte subandino de Yopal. 78 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données de la naturaliste Anna Even. 15 records from Happywhale - Peale's Dolphin in South Atlantic Ocean. 358 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de François BRETON. 816 records from Espèces végetales sur sable roux du fourré de Ranobe, PK 32 Toliara. 4368 records from Phytoplankton abundance in the Wadden Sea off List, Sylt, North Sea in 2004. 11840 records from Coral Reef Evaluation and Monitoring Project Florida Keys 1998. 273 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/108-3. 368 records from UNCW Aerial Survey 1998-1999. 95 records from Kystfuruskoger i Tysnes og Fusa. 5 records from Regroupement d'études et inventaires - Suivi Pies-grièches. 24430 records from EDP Foz Tua: Terrestrial Birds, Winter (point counts) - Ecological Monitoring Program [2011-2017]. 14 records from (Table 4b) Biomass of Emiliania huxleyi and its role in total biomass of phytoplankton along the section from the Pribilofs Islands to the Nunivak Island on 24-25 August 2001. 377 records from Inventaires et suivis faune - Inventaire et suivi des libellules – Protocole STELI. 8 records from Die Bachspezies 2008/2009. 259 records from Suivi temporel des Odonates - Inventaire et suivi Odonates – Protocole STELI. 4722 records from Atlas of Bats from Continental Portugal 2013. 1252 records from Censos de aves en los municipios de Honda (Tolima) y Guaduas (Cundinamarca) - BIO Alas, cantos y colores. 45643 records from Données Faune Base SIRFF - FNE Centre-Val de Loire - Système d’Information Régional sur la Faune et la Flore - FNE Centre-Val de Loire - Données 2016. 5361 records from Réseau de suivi des macro-invertébrés aquatiques - Inventaire et suivi Macroinvertébrés. 5640 records from Solenosmilia matrix annotations and VME habitat identification in video from voyage IN2018_V06, Australia (2018). 68 records from Streuobstwiese. 2994 records from SIM-Fungal records compiled by Joan Montón. 121 records from BIRDRACE - The famous Grouse feat. The James. 358 records from Numérisation des données faune contenues dans les Bulletins de la Société Linnéenne de Bordeaux - Bulletin de la Société Linnéenne de Bordeaux, Tome 152 (N.S) n°45 (2), 2017 - Données faune. 760 records from Total foraminifera counts of multinet M21/2_MSN650. 6702 records from Antarctic Amphipod Crustaceans: Ant'Phipoda Database (BIANZO). 7 records from Artenerhebung im Wiesenlautersystem/Pfälzerwald. 1190 records from Coleópteros presentes en un proceso de restauración pasiva en bosque seco tropical. 2484 records from Wintering wildfowl in Portugal – 1992-1993. 173 records from Manx Wildlife Trust - Records. 10692 records from TOPP Summary of SSM-derived Telemetry. 53 records from Leopard and Weddell seal program 1999/2002. 4852 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de Ségolène FAUSTEN. 62 records from Distribución, abundancia y efectos nocivos de tres especies de plantas invasoras (Oeceoclades_bonampak). 3770 records from Spatial and temporal ichthyofauna community of a tropical mangrove Bay (Gazi Bay, Kenya) sampled between 1994 and 1996. 3 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station SEPT-1998-IR64. 1 records from Happywhale - Layard's beaked whale in Southern Ocean. 378 records from (Table 2) Nannofossil occurrence in ODP Hole 101-627B. 662 records from Alterra (NL) - Microarthropods inventory in grassland and arable land. 366 records from Loup 2015 présence occasionnelle communale (réseau Loup-Lynx ONCFS). 72 records from Lebensraum Fluß/Zwickauer Mulde in Wolkenburg. 345 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données arachnologiques de LEUCHTMANN Maxime. 1 records from Karpfenteich, Klasse 6d. 912 records from Total foraminifera counts of multinet SO117_MSN1244. 485 records from Rothschild Giraffe occurrence records observed at Mwea National Reserve in Central part of Kenya. 1695 records from Happywhale - Humpback Whale in Arctic Ocean. 93 records from UNCW Hatteras Aerial Survey - Right side - 2015. 262 records from Chronicle of Nature - Phenology of Mushrooms of Pechoro-Ilych State Nature Reserve. 9174 records from Relevés of Main Vegetation Types of the Prioksko-Terrasnyi Biosphere Reserve (2019-2020). 426 records from Numérisation des données faune contenues dans les Bulletins de la Société Linnéenne de Bordeaux - Bulletin de la Société Linnéenne de Bordeaux, Tome 144 (N.S) n° 37 (3), 2009 - Données faune. 160 records from Acquario di Genova, Delfini Metropolitani Project, cetacean sightings 2001-2009. 26 records from HRC USWEX Aerial-Based Monitoring Surveys 2007. 837 records from Inventaires et suivis programme Lagunes mené par le Département des Landes - Ensemble des données Rhopalocères. 287870 records from Florida Keys Reef Visual Census 2014. 835 records from Seabird temporal composition, abundance and habitat use in “Punta La Metalera” (Arequipa), Southern Peru. 424 records from Length, width and weight of Echinotrix diadema and E. Calamaris species sampled in Mombasa Marine National Park (Kenya) from December 1994 to March 1995. 197 records from ABC_Event data recorded on a day trip to Mongolwe and Chikala Hills Forest Reserve, Machinga District. 352 records from (Table 4) Distribution of Cretaceous calcareous nannofossils in ODP Hole 114-700B. 7 records from Parasitoides de Cochinilla. 81 records from Rückkehr der Biber in Rheinland-Pfalz - Biber in der Primmerbach. 247 records from Flora vascular y no vascular: expedición Cuenca Media del río Chicamocha - Proyecto Boyacá BIO UPTC. 282 records from Migratory shorebirds (sandpipers and plovers) in Hokkaido. 2785010 records from Bryophyte data for Great Britain from the British Bryological Society held by BRC: Atlas 2014. 272769 records from NRW Regional Data: South East Wales Non-sensitive species. 227 records from Aves de la expedición en el páramo El Valle, Boyacá - Proyecto Boyacá BIO. 278 records from Saisie de données naturalistes d'observateurs indépendants sur la plateforme de l'Observatoire FAUNA - Données naturalistes de Joana PERRODIN. 536 records from Phytoplankton abundance in surface water in August 1997, Pisco, Peru. 1016 records from Suivi des oiseaux de passage : programme ACT - Programme ACT : Répartition Merle noir 2012 - 2016 Coordonnées GPS Lambert 93. 1 records from Nano and microzooplankton abundance and biomass at station NBP97-01-13-4. 372 records from Recursos hidrobiológicos de sistemas cársticos en el municipio de El Peñón, Santander - Proyecto Colombia BIO. 19 records from Small Cow-wheat distributions for Scotland 1999 to 2005. 273 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/014-6. 144 records from Diet, Tidal and Vertical Variations of Phytoplankton and Its Environment in Frobisher Bay, Canada, 1980 and 1981. 4632 records from Inventaire de la flore de la Vienne 2009-2018 - Inventaire de la flore du Grand Poitiers 2009. 33 records from Waldstück am Schullandheim Bad Bederkesa. 29 records from Occurrence of mammalia relicts at site Goyet Cave 3. 1930 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données de la naturaliste Lemoine Delphine provenant de la base de donnée du SINP Île-de-France CETTIA. 362 records from Modelación de la distribución y abundancia de las subespecies de venado cola blanca en México: implicaciones de conservación y manejo. 4570 records from Biogeography of near-shore reef fishes in northern New Zealand. 871 records from Happywhale - Leopard seal in Southern Ocean. 558 records from SOCAL FZN4 Marine Mammal Aerial Monitoring 2013. 38918 records from Diversité et répartition des mammifères non-volants d'Auvergne (Groupe Mammalogique d'Auvergne - LPO Auvergne) - Données de Carnivores collectées ou analysées par le Groupe Mammalogique d’Auvergne.. 191 records from Steinbruch Mainz-Weisenau, 2. Jahr. 9055 records from NE Scotland other invertebrate records 1800-2010. 1140 records from Plasm bearing foraminifera counts from multinet SO119_MSN1281. 1 records from Happywhale - North Atlantic Right Whale in North Atlantic Ocean. 570 records from Total foraminifera counts of multinet M10/2_MSN262. 2174 records from ConDidact Citizen Science Surveys - Snails 2006. 109 records from Birdrace-Di_Bi_Di_Birder-Wesel. 25 records from Données opportunistes faune du Groupe d'Étude et de Protection des Oiseaux en Guyane. - Données d'observations de Mammifères marins de Guyane issues de www.faune-guyane.fr. GEPOG et LPO. 306 records from (Table 1.2.1.1) Abundance of sympagic meiofauna of sea-ice core PS69/549-2. 1140 records from Total foraminifera counts of multinet M21/5_MSN742. 1544 records from Base de datos de la flora de la Reserva de la Biosfera Chamela-Cuixmala, Jalisco, México. 99 records from Schwanner Warte / Kinderhaus St. Elisabeth Waldplatz. 98 records from Regroupement d'études et inventaires - Données opportunistes sur les odonates. 345 records from Orchideenstandort Nostengraben - Kretzberg (Oßmaritz). 46 records from Schulgelände (Wetter). 278 records from Deponie Klausdorf. 67 records from Plan de gestion 2019 - 2023 de la Réserve Naturelle Régionale de l’Étang de Chourroumillas (64) mené par le CEN Nouvelle-Aquitaine - Observations d'odonates (imagos) réalisées par le CEN Aquitaine selon le protocole STERF. 285 records from Census of animals species through Benin from 2011 to 2019. 12 records from 2017 Onwards Rare Invertebrates in the Cairngorms Shining Guest Ant Survey Data. 16877 records from Inventaire des coléoptères saproxyliques de France métropolitaine - Données Entomologiques A. HORELLOU 1988-2018. 22 records from Kuhwiese Beerentaltrift (Hamburg/ Harburg). 285 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du/de la naturaliste Cousin Richard provenant de la base de donnée du SINP Île-de-France CETTIA. 3090 records from Establecimiento de un área protegida en el Alto y Bajo Calima, área clave de biodiversidad en el Valle del Cauca, Colombia. 247 records from DUML vessel-based photo-id and biopsy surveys for proposed JAX USWTR site 2012-2015. 14391 records from Enquêtes de l'Opie - Enquête Lucane. 54 records from Phytoplankton abundance at station Casma_2003-04-28_2, Casma, Peru. 947 records from Erlengraben/Lipp-Tal (Östringen). 310 records from Records of Halicarcinus planatus at sub-Antarctic regions. 1986 records from Inventaire des coléoptères saproxyliques de France métropolitaine - Observations de Coléoptères saproxyliques de Frédéric LACOSTE. 56582 records from Birds of Rottnest Island, Western Australia, 1981 - 2007. 1140 records from Plasm bearing foraminifera counts of multinet M21/2_MSN656. 392 records from Inventaire des invertébrés marins benthiques et des algues de la Guadeloupe : expédition Karubenthos 2012 - Expédition Karubenthos 2012 : inventaire des Echinodermes de la Guadeloupe. 1489 records from Population research on small rodents (Rodentia) and shrews (Soricidae) in Steinkjer Municipality – Norway; 1996 - 2017 based on systematic catches with ordinary mouse traps in traplines. 160 records from EDIT - ATBI in Gemer area (Slovakia). 903 records from (Table 3) Distribution of Pleistocene to late Miocene nannofossils in ODP Hole 108-657A. 2 records from Saisie de données naturalistes d'observateurs indépendants sur la plateforme de l'Observatoire FAUNA - Données naturalistes de Frédéric NOILHAC. 325 records from Mollusques continentaux de France - Inventaire malacologique de la RNR des Marais de Stors. 88 records from Teich Berlin Wuhlheide. 19 records from Microplankton data off Mejillones, 2006, Chile. 1110 records from (Table 2) The presence and absence of whole and/or fragmented planktonic and benthic foraminifers at DSDP Hole 93-603. 112 records from Creag Riabhach Wind Farm: 2012-13 Ornithology and Protected Mammal Surveys. 150 records from AKG-Gelände (Bensheim). 1 records from Animation du Document d’objectifs du site Natura 2000 FR7200664 - Coteaux calcaires de la vallée de la Dordogne (24) menée par le CEN Nouvelle-Aquitaine - Observations faunistiques fortuites réalisées par le CEN Aquitaine. 949700 records from Flora Atlas N.T.. 115 records from Diagnostic écologique et élaboration d'une notice de gestion (prairies humides et calcaires) sur la commune de Monflanquin (47) menés entre 2017 et 2022 par le CEN Nouvelle-Aquitaine - Observations faunistiques fortuites réalisées par le CEN Aquitaine. 8 records from Sarcodine counts and carbon biomass at station TT012_5-TM9. 1 records from Klosterlandschaft Maulbronn 19. und 20. Juni 2010. 5426 records from Fishes in the Argentine Sea from 1967 to the present time. 324 records from Herbaceous and arboreous plants list on the Komaba Campus of University of Tokyo, Japan. 1 records from Occurrence of mammalia relicts at site Raagelund. 59 records from ONCFS Réseau Ours brun - Ours 2007 présence Occasionnelle Mailles 10km LAEA Réseau Ours brun ONCFS. 5 records from Projet de port de plaisance de Brétignolles sur Mer - Mammifères - Inventaire non protocolé. 10919 records from Fish observations delivered by "Canarias por una Costa Viva" project. 348 records from Naturschutzgebiet Heiliger Hain (Wahrenholz). 3 records from Nano and microzooplankton abundance and biomass at station NBP96-04A-13-4. 218 records from Étude préalable à la création d’une Réserve Naturelle Régionale des landes périgourdines menée par le CEN Aquitaine - Observations faunistiques (inventaire) réalisées par le CEN Aquitaine. 829 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données de la structure SNPN - Société Nationale de Protection de la nature provenant de la base de donnée du SINP Île-de-France CETTIA. 795 records from Walter Herwig 1978 (FFS): SeaStars (Echinodermata, Asteroidea). 10699 records from Atomariine Beetle (Coleoptera) records for Britain and Ireland to 1992. 2718 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données de la Réserve Naturelle Nationale de Saint-Quentin-en-Yvelines provenant de la base de donnée du SINP Île-de-France CETTIA. 845 records from Alterra (NL) - Entomofauna inventory in arable fields Hoeksche Waard. 139 records from Occurrence of zoobenthos organisms in the sampled Central-Yakutian Lakes, Appendix 2-4. 8 records from Saisie de données naturalistes d'observateurs indépendants sur la plateforme de l'Observatoire FAUNA - Données naturalistes de Richard DENEUVIC. 129 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du/de la naturaliste jourdan christian provenant de la base de donnée du SINP Île-de-France CETTIA. 1024 records from Suivi des oiseaux de passage : programme ACT - Programme ACT : Répartition Grive draine 2001 - 2005 Coordonnées GPS Lambert 93. 49 records from Projet photovoltaïque au sol de Marigny - Terre Neuve (79) - Volet "autre faune" - projet photovoltaïque de Marigny - Terre Neuve (79). 5 records from Microzooplankton abundance and biomass at station NBP97-08-05-1. 25692 records from Liste des insectes associés au Vitellaria paradoxa C. E Gaertner, au Centre et au Nord du Bénin. 5 records from Parc éolien de la Société d’Exploitation du Parc Eolien des Noues à Blacy (51) - Inventaire non protocolé des mammifères terrestres. 209 records from Lebensraum Gesamtschule (Langerwehe). 165 records from Antarctic Amphipoda. 14 records from Observations naturalistes indépendantes d'origine privée partagées sur la base de données Kollect Nouvelle-Aquitaine - Observations faunistiques de Kathy FOOT. 1654 records from RAVON (NL) - Fish observations extracted from Redeke (1907). 95950 records from Butterflies of Ireland. 4 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de Jean-Yves BOUTET. 779 records from Centrale solaire Zac de l'Empereur - Etude d'Impact Données Faune/Flore. 580 records from Rare plants database extract from Scottish Natural Heritage. 2508 records from Données des collections du MNHN - Données des collections d'algues du MNHN. 939 records from Les Coléoptères Silphidés du département du Loiret. 760 records from Total foraminifera counts of multinet M21/2_MSN648. 68377 records from CSIRO, Cruises, Vertebrate and Invertebrate Fishery Bycatch, North Australia, 1997. 422150 records from NOAA AFSC North Pacific Groundfish Observer. 15387 records from Formidabel; Belgian Ants Database. 3272 records from Données Association Évasion tropicale (AET) - Mammifères marins Guadeloupe Antilles françaises (AET). Suppléments. 456 records from Ferme pilote d'éoliennes flottantes de Groix & Belle-Ile et son raccordement au Réseau Public de Transport d'Electricité - Campagne d’investigations ichtyofaune – Ferme pilote de Groix & Belle-Ile. 118 records from BD de la plateforme partagée pour la diffusion des données naturalistes de Haute-Normandie - Observation des insectes sur le territoire de la Métropole Rouen Normandie. 192 records from Alterra (NL) - Microarthropods inventory in Cranendonck area. 401 records from Anfibios y reptiles de la Sierra Montenegro-Las Trincheras y el cerro el Chumil, Morelos. 1148 records from ABC event data for Nyika Plateau, Buma Hills. 16 records from Hazel Dormouse in Ireland. 34 records from Geographical distribution and abundance of the land blue crab Cardisoma guanhumi (Brachyura, Gecarcinidae) in Venezuela. 41 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Etude d'impact projet d’ouverture de carrière à Vaudoy-en-Brie. 7 records from Projet de parc éolien de la Croix Guingal, sur la commune de Derval (44 590) - Croix Guingal - chiro - transit printanier 2014. 1036 records from Suivi des oiseaux de passage : programme ACT - Programme ACT : Répartition Merle noir 1996 - 2000 Coordonnées GPS Lambert 93. 49 records from (Table 2) Benthic foraminifers at DSDP Hole 72-515A. 47 records from Happywhale - Short-beaked Common Dolphin in North Pacific Ocean. 43 records from Projet éolien de Saint-Barbant - Autre faune. 36 records from Réseau Loup - Lynx ONCFS - Lynx 1992 présence Régulière Mailles 10km Réseau Loup-Lynx ONCFS. 504 records from Programme les sentinelles du climat - effets du changement climatique sur la biodiversité en région Nouvelle-Aquitaine - Observations d'odonates réalisées par le CPIE Seignanx et Adour selon le protocole STELI adapté pour le programme. 243 records from Fish species occurrences from selected near shore and riverine habitats in Lake Edward (2019). 9257 records from Service National d'Observation CORAIL - Réseau de surveillance Polynesia Mana - Peuplements de poissons. 1617 records from Helmintos parásitos de peces del sureste de México. 1 records from Saisie de données naturalistes d'observateurs indépendants sur la plateforme de l'Observatoire FAUNA - Données naturalistes de Olivier LE GALL. 383 records from Inventario de Peces del SFF Isla Malpelo, Proyecto Colombia Bio. 112 records from UNCW Norfolk Canyon Aerial Survey - Right side - 2015. 61 records from Naturpark Kottenforst-Ville 15.6.09. 1031 records from ConDidact Citizen Science Surveys - Spiders 2011. 1087 records from Tree species composition of natural forest islands in a savanna matrix in the northern Brazilian Amazonia. 368 records from HogWatch Scotland Project - West European hedgehog records between 2019 and 2021. 83 records from Roter Berg Werdau (Leubnitz). 222 records from Land and freshwater molluscs of Northern Spain. 1677 records from The Belgica 121 expedition to the Western Antarctic Peninsula: a high resolution biodiversity census. 21 records from Carpoteca de Frutilla del Banco de Germoplasma de Frutilla - Universidad Nacional de Tucumán, Argentina. 37 records from Happywhale - Killer Whale in Arctic Ocean. 3785 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de Charlotte PICARD. 950 records from Total foraminifera counts of multinet M21/4_MSN706. 760 records from Plasm bearing foraminifera counts of multinet M21/1_MSN615. 131 records from Manejo campesino sustentable del maguey papalote del Chilapan. Fase II. 173 records from FFH-Gebiet Klosterwasser/Burkau. 1 records from University of California Santa Barbara Invertebrate Zoology Collection. 319 records from Seasonal variation of the zooplankton community at Gazi, Lamu and Malindi (Kenya) sampled between 1990 and 1992. 395 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de Hubert GUIMIER. 6447 records from Fish occurrence in Kama River basin. 1864 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de Hervé BOUYON. 1808 records from Inventaire des coléoptères saproxyliques de France métropolitaine - Données de la collection Rousset -1947-2013. 117 records from Cnidarios y Poriferos del Parque Nacional San Esteban, Venezuela. 76 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du/de la naturaliste D'HINZELIN MARCEL provenant de la base de donnée du SINP Île-de-France CETTIA. 17 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Anhingidae. 57 records from (Table 2) Distribution of recurrent planktonic foraminifera at DSDP Hole 75-530A. 1015 records from Suivi des oiseaux de passage : programme ACT - Programme ACT : Répartition Grive musicienne 2004 - 2008 Coordonnées GPS Lambert 93. 1140 records from Plasm bearing foraminifera counts from M35/1_MSN1048. 1176 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Observations naturalistes d'Hervé BRUSTEL. 19 records from Plan de gestion 2017 - 2021 de la Réserve Naturelle Régionale d'Errota Handia (64) mené par le CEN Nouvelle-Aquitaine - Observations faunistiques (suivi par piège photographique) réalisées par le CEN Nouvelle-Aquitaine. 136 records from Réseau Loup - Lynx ONCFS - Lynx 2005 présence Occasionnelle Mailles 10km Réseau Loup-Lynx ONCFS. 57 records from CSIRO Yellow Box Fragmentation Project. 760 records from Total foraminifera counts of multinet M21/2_MSN629. 5246 records from 台灣花蓮沿海賞鯨活動鯨豚觀測紀錄 (The observation records from the activities of whale and dolphin watching in the offshore of Hualien, Eastern Taiwan). 867 records from Étude des invertébrés sur les sites Natura 2000 de l'estuaire de la Gironde - Inventaire lépidoptère et odonate. 40 records from makran-chabahar-arthropods. 109 records from Plan de gestion des Marais du Conseiller - Inventaire et suivi Rhopalocères – Protocole PROPAGE. 602 records from NMML Small Cetacean Aerial Survey 1997. 3213 records from Données DREAL Centre-Val de Loire - Faune - 2018. 169854 records from Locations of plants on dot distribution maps in the Flora of Siberia (Flora Sibiraea, 1987–1997). 114 records from BIRDRACE LiLaLau. 912 records from Total foraminifera counts of multinet POS247/2_MSN1372. 54670 records from Tetraonid line transect surveys from Norway: Data from Fjellstyrene. 53 records from Observations naturalistes indépendantes d'origine privée partagées sur la base de données Kollect Nouvelle-Aquitaine - Observations faunistiques de Pierre DUCAMP. 1313 records from Fish occurrence in Kuban River basin. 39 records from Schulteich Freie Waldorfschule Darmstadt. 9054 records from Highland bird data 2002 - 2003 - non-breeding records. 684 records from Inventario de Flora de la Reserva Forestal Protectora Regional Cuchillas del Tigre, El Calón y La Osa. Municipios de San Francisco y Sonsón-Antioquia.. 8446 records from 1994-2021 Capercaillie Cold Searches Data, Scotland. 130 records from ABC_Ndangopuma_hills_eventdata_25_11_2005. 46580 records from Weed and native flora data for the Swan Coastal Plain. 38710 records from A dataset of bird inventory records at Cloudbridge Nature Reserve, Talamanca Mountains, Costa Rica, between March 2016 and May 2020.. 912 records from Total foraminifera counts from M35/1_MSN1061. 950 records from Plasm bearing foraminifera counts of multinet M21/2_MSN627. 96 records from Observatoire des sites majeurs - LEYRE - Inventaire et suivi Loutre d'Europe. 4159 records from Réserves Naturelles de France (RNF) - RNF - Données du Parc Naturel Régional du Vercors. 74 records from Projet de lotissement sur la commune de Martillac - Inventaire faune. 181 records from UNCW Norfolk Canyon Aerial Survey - Left side - 2016. 206 records from Registros de geckos en Colombia asociado al proyecto: The small world of Lepidoblepharis. 3109 records from Insectes Hyménoptères Scoliidés de France - Insectes Hyménoptères Scollidés de France. 3621 records from POPA- Fisheries Observer Program of the Azores: Turtle sightings in the Azores tuna fishery from 2000 on: during navigation or search mode.. 178 records from Projets photovoltaïques de Sablirot Sud et Nord - Inventaires écologiques. 1153 records from Inventaires et suivis programme Lagunes mené par le Département des Landes - Ensemble des données Odonates. 1875 records from Phytoplankton abundance during Gunnar Thorson cruise GT90/5. 884 records from Diversité et distribution de quelques espèces de plantes agroforestières au Bénin. 569 records from Inventario y monitoreo del Canal de Infiernillo para el comanejo de los recursos marinos en el territorio Seri, Golfo de California. 1140 records from Total foraminifera counts of multinet M36/6_MSN1196. 4 records from Saisie de données naturalistes d'observateurs indépendants sur la plateforme de l'Observatoire FAUNA - Données naturalistes de Valentin LECONNET. 31 records from Transfert de fichier de données naturalistes d'observateurs indépendants à l'Observatoire FAUNA - Données naturalistes de Stanislas WROZA. 4717 records from Weddell Sea macrozoobenthos EASIZ I. 916 records from IOW Natural History & Archaeological Society Marine Records. 950 records from Total foraminifera counts of multinet M21/4_MSN694. 52613 records from Insects, Outer Hebrides. 119 records from Suivis des sites gérés par la Fédération des Chasseurs des Landes - Suivi des leucorrines sur le site du Marais du Plata. 46 records from An der Ohm, (Wettsaasen). 88 records from Phytoplankton abundance at station Rigel_4_2005-08 in August 2005, Chipana, Chile. 29986 records from EDP Baixo Sabor: Construction and Reservoir Filling Phases – Vascular Flora and Habitats: species of conservation concern (RELAPE) - [2010-2014]. 185 records from Elaboration du DOCOB du site Natura 2000 ‘Réseau hydrographique des affluents de la Midouze’ (FR7200722) - Inventaire des odonates d'intérêt communautaire. 4 records from 76 - Bois de Beaumont - Amphibiens. 168 records from Restauración de flora y repoblamiento de fauna nativa en 1,000 hectáreas para el restablecimiento del corredor biológico costero en la Laguna Madre, Tamaulipas. 69 records from Сypripedium guttatum Sw. in the Komi republic. 2419 records from Flora de las sabanas inundables de las cuencas de los ríos Bita, Manacacías y Cravo Sur - SULU II. 1 records from Saisie de données naturalistes d'observateurs indépendants sur la plateforme de l'Observatoire FAUNA - Données naturalistes de Stéphane DULAU DULAU. 515 records from Kenai National Wildlife Refuge, Alaska (KNWR) Bird observations (Arctos). 13527 records from Distribution Atlas of Butterflies in Ireland 1979 (An Foras Forbartha). 9 records from Projet Courlis cendré et avifaune associée - Inventaire Avifaune. 43 records from Reptiles de la Ecoreserva Refinería (Santander, Barrancabermeja) - Proyecto FIBRAS. 1 records from Etat des lieux des suivis effectués dans le cadre de la LGV SEA - Suivi Avifaune Lande sèches. 2339 records from NSW South Coast & ACT plants. 52 records from Projet du parc éolien de la Voie des Prêtres 2 - Liste de l'avifaune recensée en période de reproduction 2015. 8848 records from EDP Baixo Sabor: Birds - Construction and Reservoir Filling Phases - Vilariça Stream (MC1) [2013-2014]. 1306 records from Atlas de la Biodiversité Communales sur la Communauté de Commune de Montesquieu - Inventaire des Orthoptères dans le cadre des ABC de la CC de Montesquieu. 8410 records from Aves Acuáticas de las sabanas inundables del Meta y Casanare. 1 records from Happywhale - Ringed Seal in North Atlantic Ocean. 253 records from Données naturalistes d'Olivier LAURENT. 77 records from (Fig. 10) Distribution of dinoflagellate cysts in Early Cretaceous sediments of DSDP Hole 41-367 in the North Atlantic. 24260 records from Restauración y conservación de Isla Guadalupe. 396 records from (Table 2) Species composition of algae and cyanobacteria encountered in plankton of the Large Aral Sea on June 2-8, 2008. 72 records from Animation du Document d’objectifs du site Natura 2000 FR7200799 - Carrières de Castelculier (47) menée par le CEN Nouvelle-Aquitaine - Observations faunistiques (inventaire) réalisées par le CEN Aquitaine. 46 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Caprimulgidae. 45 records from Natterjack Toads of Ireland. 83 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Polioptilidae. 15295 records from Biodiversidad asociada al gasoducto Paiva-Caracolí. 993 records from ROC RSPB Farmland Species Survey Dataset. 96 records from Warnowtal (Rostock). 152 records from Numérisation des données faune contenues dans les Bulletins de la Société Linnéenne de Bordeaux - Bulletin de la Société Linnéenne de Bordeaux, Tome 135 (N.S) n° 28 (4), 2000 - Données faune. 22 records from Site Condition Monitoring of dragonflies on Loch aí Mhuilinn SSSI potential extension - 2016. 205 records from Wild boar sightings held by Andy Riches. 198 records from Chronicle of Nature - Phenology of Birds of FSBI United Administration of the Lazovsky State Reserve and National Park Zov Tigra. 124 records from Chronicle of Nature - Phenology of Insects of Baikalsky State Nature Biosphere Reserve. 8464 records from Community Foundation for Ireland Records. 6 records from Wuhle - Brücke / B1. 182049 records from Florida Keys Reef Visual Census 1999. 164 records from Identification et caractérisation des peuplements entomologiques des landes - Inventaire Coléoptères. 60 records from Individuos de Gunnera schultesii L.E.Mora y su respuesta al efecto de la sombra y el tipo de fertilizante sobre su crecimiento en condiciones ex situ. 489 records from Caracterización bionómica de zonas de dragado y de afección de obras en la Ría de Ferrol. 382 records from Poliquetos fondos arenosos de Arrecifes de Coral en el PN Archipiélago de Los Roques, Venezuela. 755 records from Composición florística y estructura de tres parcelas permanentes en diferentes estados sucesionales en transición de bosques húmedos tropicales con bosques secos tropicales del municipio de Lebrija, Santander (Primer censo). 12756362 records from The Danish Environmental Portal, species and habitats-database "Danmarks Miljøportals Naturdatabase". 195 records from EDP Foz-Tua: Nocturnal Birds - Complementary Studies [2010]. 17 records from Plan de gestion 2016 - 2020 du site du domaine de Rodié (47) mené par le CEN Nouvelle-Aquitaine - Observations faunistiques (suivi par dénombrement) réalisées par le CEN Aquitaine. 16 records from Phenological Center - Fishes (Murmansk). 9 records from Steinbock (1937) Turbellaria XIV. The fishery grounds near Alexandria. Notes and Memories of the Fisheries Directorate of Egypt, No. 25. 46 records from Phenological Center - Mushrooms (Karelia). 358 records from Comunidad fitoplanctónica presente en la Bahía de Buenaventura 2018. 10 records from Occurrence of mammalia relicts at site Meiendorf. 63 records from Occurrence of mammalia relicts at site Laugerie-Haut e-Est. 111 records from BIRDRACE Die Wendehälse. 22586 records from Tachinid Recording Scheme - GB and Ireland records. 172 records from SEFSC GoMMAPPS Vessel Survey 2018 Summer. 286 records from Abundance and biomass of phytoplankton in Butakova Bay, Aral Sea, in september 1990. 98 records from Plan de gestion multi-sites à Chiroptères mené par le CEN Aquitaine depuis 2008 - Observations de chiroptères (suivi par dénombrement) réalisées par le CEN Nouvelle-Aquitaine. 1 records from Plan de gestion 2018 - 2022 du site de la Butte de la Lot (33) mené par le CEN Nouvelle-Aquitaine - Observations faunistiques (suivi par dénombrement) réalisées par le CEN Aquitaine. 3230 records from Phytoplankton abundance and species composition in the Gulf of Naples and the Gulf Salerno in November 1985. 1 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Pandionidae. 8332 records from Scotland Otter Survey Database. 5 records from Saisie de données naturalistes d'observateurs indépendants sur la plateforme de l'Observatoire FAUNA - Données naturalistes de Mikaël PAILLET. 558 records from Phytoplankton abundance and species composition in the Gulf of Naples in June 1999 at station MCSSII-phyto120-128. 4617 records from Données du Parc National de la Guadeloupe - Données de type contact en Guadeloupe. 351788 records from Kastikka Floristic Archives (KEVO). 1332 records from Inventaire Entomologique, E. DECAUX 1998 - Inventaire des données récoltées par Emmanuelle DECAUX et la SEL. 11 records from Saisie de données naturalistes d'observateurs indépendants sur la plateforme de l'Observatoire FAUNA - Données naturalistes de Charles BRESSON. 210 records from Microzooplankton abundance measured on water bottle samples at station PS65/570-4. 656 records from Herpetofauna de la región del Mar Muerto, Oaxaca-Chiapas. 36 records from Inventaire en continu de la ZNIEFF 'Prairies Du Loubet Et Du Tolzac' - 720020107 - Prairies du Loubet et du Tolzac - Inventaire Oiseaux, Amphibiens & Reptiles opportunistes. 331 records from Projet éolien de Plestan II - Volet chiroptère/étude en altitude. 223486 records from Phytochorologie des départements français. 5772 records from A grid-based database on vascular plant distribution in Samoylovsky District of Saratov Oblast, Russia. 1 records from Saisie de données naturalistes d'observateurs indépendants sur la plateforme de l'Observatoire FAUNA - Données naturalistes de Mathieu TAILLADE. 21 records from "Natur macht Schule 2" Natur im Wohngebiet Gorndorf. 264 records from Microplankton abundance at Station MARCH-1997-GN36199704601MSB07 in the euphotic zone of the Aegean Sea in spring 1997. Part 1 - diatoms. 18 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT011_5-CTD58. 2 records from Plan de gestion 2013 - 2018 du Lac de La Prade (33) mené par le CEN Aquitaine - Observations faunistiques (suivi par dénombrement) réalisées par le CEN Aquitaine. 199 records from Demospongias de la Laguna La Restinga, Venezuela. 1000 records from SEFSC Mid-Atlantic Tursiops Survey, 1995 3. 1591 records from Ornithological observations in the Kharkiv region of Ukraine. 2070 records from Données du Parc National de la Guadeloupe - Atlas des Poissons et Crustacés d'eau douce de Guadeloupe. 664 records from Inventario multitaxonómico del ANP Médanos de Samalayuca. 245166 records from Programme CarNET B (Cartographie Nationale des Enjeux Territorialisés de Biodiversité Remarquable) - Carnet B Lorraine. 31 records from Ecosystems of the sandstone region incl. sand-belt (SE of Melb.). 1037 records from Evaluación del estado actual de las poblaciones silvestres de chigüiros (Hydrochoerus hydrochaeris) en los municipios de Paz de Ariporo y Hato Corozal, Casanare. 49 records from Mamíferos de la Ecoreserva Predio Isla IV (Cantagallo, Bolívar) - Proyecto FIBRAS. 2 records from Développement du pôle commercial de Peyssilieu (Meyzieu 69) - Inventaire orthoptère_Meyzieu -pôle commercial de Peyssilieu. 61825 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du/de la naturaliste Bottinelli Julien provenant de la base de donnée du SINP Île-de-France CETTIA. 72 records from Atlas de la Biodiversité Communales sur la Communauté de Commune de Montesquieu - Observations d'orthoptères (inventaire) réalisées par Locusta. 380700 records from Seasearch Marine Surveys in England. 912 records from Plasm bearing foraminifera counts of multinet M21/2_MSN657. 644 records from Bibliographie de la faune, la flore et la fonge de France métropolitaine et outre-mer - Annales de la Société Linnéenne de Maine-et-Loire. 122 records from Comunidad íctica del atolón Albuquerque durante la Expedición Seaflower 2018 - Proyecto Colombia BIO. 199 records from Bibliographie de la faune, la flore et la fonge de France métropolitaine et outre-mer - Données de Mammifères marins dans les TAAF et autres territoires issues de la bibliographies. Compte cardobs 1007 (Trudelle). 12 records from Développement du pôle commercial de Peyssilieu (Meyzieu 69) - Inventaire lépidoptère_Meyzieu - Pôle commercial de Peyssilieu. 4 records from projet photovoltaique l'epine - Inventaire des mammifères pour le projet de parc photovoltaïque de l'Epine. 3 records from e-Valley, le plus grand parc e-logistique d'Europe - Mammifères terrestres - Inventaire non standardisé. 500 records from Chronicle of Nature - Phenology of Insects of Pechoro-Ilych State Nature Reserve. 117 records from PROJET DE CENTRALE PHOTOVOLTAÏQUE SAINTE ANNE LA ROCHE SUR YON - Inventaire espèces presente sur site. 55 records from Mollusques continentaux de France - Données malacologiques continentales de Julien Ryelandt (CORSE 2017). 25 records from Swiss Occurrence Records of Native Species of Various Faunal Groups. 14168 records from Insectes Hétéroptères Mirides de France. 46 records from Parc éolien d'Argillières - ornithologie reproduction. 160 records from Integrierte Gesamtschule Flensburg Wiemoosgraben. 6 records from Happywhale - Arnoux's Beaked Whale in Southern Ocean. 1552 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du naturaliste ROCHAT Didier provenant de la base de donnée du SINP Île-de-France CETTIA. 1 records from Happywhale - Long-finned Pilot Whale in North Pacific Ocean. 5305 records from Mutualisation des données naturalistes pour le rapportage Natura2000 en 2017 - Synthèse 10x10km des espèces de la Directive Oiseaux recensée par le Groupe Ornithologique des Deux-Sèvres de 2013 à 2017. 23 records from Numérisation des données faune contenues dans les Bulletins de la Société Linnéenne de Bordeaux - Bulletin de la Société Linnéenne de Bordeaux, Tome 135 (N.S) n° 28 (1), 2000 - Données faune. 93 records from Projet éolien - Insectes - Inventaire non protocolé. 115 records from Abundances of dinoflagellate cysts in sediment trap MST-9 (Appendix 1). 184 records from Occurrence of mammalia relicts at site Raj Cave. 1022 records from Suivi des oiseaux de passage : programme ACT - Programme ACT : Répartition Caille des blés 2000 - 2004 Coordonnées GPS Lambert 93. 3740 records from Chronicle of Nature - Phenology of Plants of State Nature Reserve Olekminsky. 494248 records from BLS Mapping Scheme dataset, 1750-2009. 74 records from Anfibiofauna asociada a la quebrada Giginia, corregimiento de Doña Josefa, Municipio del Atrato - Chocó, 2019. 297 records from Aves de la expedición en el páramo de Bijagual, Boyacá - Proyecto Boyacá BIO. 60 records from Centrale Hydroélectrique de Bouginal. 1 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes d'Olivier DELZONS. 1 records from Observations naturalistes indépendantes d'origine privée partagées sur la base de données Kollect Nouvelle-Aquitaine - Observations faunistiques de Monique CASTEX. 156 records from Coccolith counts of multinet SO119_MSN1272. 18 records from Schulgarten der Gesamtschule Am Heidberg. 180 records from (Table 2.2.1.1) Abundance of sympagic meiofauna of sea-ice core IO-11. 1273 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du/de la naturaliste Lantz André provenant de la base de donnée du SINP Île-de-France CETTIA. 162 records from Schulhof Gymnasium Hürth Bonnstrasse. 68 records from Gewässer des Wartbergparks Stuttgart (bei der Ökostation der VHS Stuttgart). 5 records from Inventur der Natur rund ums NABU-Naturzentrum in Haseldorf. 106 records from BIRDRACE Bon(n)apartemöwen. 150 records from Ferme pilote d'éoliennes flottantes de Groix & Belle-Ile et son raccordement au Réseau Public de Transport d'Electricité - Campagne faunistique terrestre - Raccordement du parc éolien Groix/Belle-île. 335 records from Composición florística y estructura de una parcela permanente en bosques húmedos tropicales del municipio de Pie de Pepe, Chocó. 4 records from Microzooplankton abundance and biomass at station NBP97-08-29-1. 1575 records from NatureMap Calcrete Survey. 62 records from Données naturalistes de BONCHE Jérôme. 4180 records from Marine Bird Sighting Data, Arctic Marine Biodiversity Observing Network (AMBON) Chukchi Sea research cruise on the vessel Norseman II from 2015-08-09 to 2015-09-03. 104 records from Réseau Loup - Lynx ONCFS - Lynx 2002 présence Occasionnelle Mailles 10km Réseau Loup-Lynx ONCFS. 32 records from Abyssal fauna of the UK-1 polymetallic nodule exploration claim, Clarion-Clipperton Zone, central Pacific Ocean: Echinodermata. 81329 records from natagora-earlybirds. 4 records from Happywhale - Spinner Dolphin in North Atlantic Ocean. 26 records from FERME ÉOLIENNE DE BLANZAY - Avifaune Blanzay hiver 2017. 11 records from Plan de gestion 2013 - 2017 du site des Coteaux de Pujols (33) mené par le CEN Aquitaine - Observations faunistiques fortuites réalisées par le CEN Aquitaine. 2534 records from Elaboration de table de tarif de cubage multispécifique (I). 431 records from Occurrences of Boeckella at high latitudes in the southern hemisphere. 22 records from Wildgehege Glauer Tal (Naturpark Nuthe-Nieplitz). 44 records from W.E.B. Parc éolien des vents du Serein - Insectes - Inventaire non standardisé. 133637 records from Mammal records from Britain from the Atlas of Mammals (1993), with some subsequent records. 393 records from Heinersdorfer Sumpfwiese. 36 records from Plan de gestion 2013 - 2018 du site des Coteaux de Las Hies (64) mené par le CEN Aquitaine - Observations faunistiques (suivi par dénombrement) réalisées par le CEN Aquitaine. 151 records from VSN-Wiese. 940 records from Données transmises au PNR Périgord-Limousin n'étant pas commanditées par le parc - Inventaire Lépidoptères réalisé par David Moore sur le plateau d'Argentine. 63085 records from Alien plant presence dataset from the point-radius plot surveys in 2010-2015 in Taiwan. 2 records from Microplankton counts and carbon biomass at station TT011_8-CTD96. 1017 records from Suivi des oiseaux de passage : programme ACT - Programme ACT : Répartition Pigeon ramier 2006 - 2010 Coordonnées GPS Lambert 93. 200 records from Programme LIFE CROAA - Phase 1 : Inventaire de répartition de la Grenouille taureau par écoutes nocturnes. 792 records from EDP Baixo Sabor: Construction and Reservoir Filling Phases: Cliff-nesting Birds, priority conservation species: Complementary Observations - [2010-2014]. 94 records from Projet de carrière - Ravine du Trou - Saint-Leu (974) - Inventaires des Oiseaux. 29 records from Fortalecimiento de la efectividad del manejo y la resiliencia de las áreas naturales protegidas para proteger la biodiversidad amenazada por el cambio climático. 659 records from (Table 15) Distribution of planktonic foraminifers in ODP Hole 108-666A. 273 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/009-6. 1486 records from Alien plants of Sterlitamak. 93644 records from SILENE-FAUNE-PACA - Amis_des_Marais_du_Vigueirat_2017_12_18. 48 records from Mollusques continentaux de France - Atelier Malacologie continentale, 14-15septembre, La Flèche (Sarthe). CEN Pays de la Loire. 76 records from BIRDRACE Nachtigallen. 1286 records from ConDidact Citizen Science Surveys - Amphibians 2007. 61 records from Inventaire des Lépidoptères Rhopalocères et Zygènes de France métropolitaine - Données de Midi-Pyrénées transmises par Pascal Peyrache.. 296 records from HRC SCC Aerial-Based Monitoring Survey February 2010. 271 records from Norfish: English North-East Atlantic cod fishery, 1520-1790. 14 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de THÉVENOT Jessica. 1140 records from Total foraminifera counts of multinet FCA97C_MSN1345. 27 records from Occurrence of mammalia relicts at site Biedermann. 20442 records from Trondheim urban biodyversity survey. 35145 records from Inventaire de la flore de Lot-et-Garonne 2013-2018 - Inventaire de la flore de Lot-et-Garonne 2017. 94 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du/de la naturaliste LUSTRAT Philippe provenant de la base de donnée du SINP Île-de-France CETTIA. 129 records from SNH Invertebrate Site Condition Monitoring 2013/14: Glenmore Forest SSSI. 280 records from Size of planktic foraminifera at CTD station PS55/083-1. 315 records from Phytoplankton abundance measured on water bottle samples at station PS65/514-2. 122 records from Inventaire chiroptérologique dans les Chataigneraies du PNRPL - Inventaire bioaccoustique et capture au filet de chiroptères en verger à châtaignes 2019. 505 records from Catalogue and description of the coccolithophores (Haptophyta, Coccolithophyceae), calcareous, scale-bearing microalgae, in New Zealand waters. 90 records from Plan de gestion du Marais du Logit - Inventaire opportuniste Faune. 660 records from Peces pelágicos de la Isla Cayo Serrana durante la Expedición Seaflower 2016 - Proyecto Colombia BIO. 413 records from Clyde Breeding Bird Tetrad Atlas 1985 - 1991 - sensitive species. 44 records from Cellule d'Assistance Technique Landes et Pelouses Sèches des Pyrénées-Atlantiques (CATLPS64) du CEN Nouvelle-Aquitaine - Observations faunistiques (suivi par dénombrement) réalisées par le CEN Aquitaine. 1 records from Saisie de données naturalistes d'observateurs indépendants sur la plateforme de l'Observatoire FAUNA - Données naturalistes de Pôle Nature MARAIS POITEVIN. 47 records from Distribución de la Nutria (Lontra longicaudis) en la cuenca baja del río Sinú en el departamento de Córdoba. 654766 records from niek_2022. 125 records from Réseau Loup - Lynx ONCFS - Réseau Loup-Lynx : Répartition communale Occasionnelle du Loup en 2009. 101 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de LE GLOANEC Vincent. 127 records from Projet photovoltaïque au sol de Marigny - Terre Neuve (79) - Volet oiseaux - projet photovoltaïque de Marigny - Terre Neuve (79). 243739 records from Calf of Man (Isle of Man) Bird Observatory Daily Logs, 1959-67, 1969-81, 1983-5. 204 records from Microplankton abundance at Station SEPT-1997-GN36199704606MNB01 in the euphotic zone of the Aegean Sea in September 1997. Part 3 - coccolithophores and other groups. 280 records from Size of planktic foraminifera at CTD station PS55/051. 792 records from Phytoplankton abundance in surface water in January 1996, Paita, Peru. 557 records from Corn bunting breeding distribution in Scotland. 7122 records from Whale catches in the Southern Ocean. 41 records from Réseau Loup - Lynx ONCFS - Lynx 1999 présence Régulière Mailles 10km Réseau Loup-Lynx ONCFS. 331 records from KARSTLANDSCHAFT SÜDHARZ - VOM GIPSABBAU BEDROHT (Grenzstreifen am Röseberg). 92 records from Foraminifera species abundances from tow TT007_7-MOC13. 21 records from Plan régional d'actions en faveur des odonates (PRAO) : 4ème phase (2019 - 2020) menée par le CEN Nouvelle-Aquitaine - Observations faunistiques fortuites réalisées par le CEN Aquitaine (Étude Leucorrhines). 88 records from Etude avifaunistique de la LPO Limousin sur les landes haut-viennoises - Inventaire et suivi Avifaune de la lande de Beaubreuil. 77075 records from CABI Africa Invasive and Alien Species data. 31361 records from River Biologists' Database (EPA). 150 records from Selztal bei Friesenheim. 40794 records from Banded Iron Formation and Greenstone survey data. 230 records from Biometría peces Parque Nacional Natural La Paya. 1651 records from Great Eastern Ranges - Slopes to Summit. 11 records from Microzooplankton abundance and biomass at station TT045_19-3. 8244 records from Tiroler Landesmuseum Ferdinandeum. 100 records from Phytoplankton abundance at station Rigel_1_2005-02 in Febraury 2005, Chipana, Chile. 82 records from Kenyan reef corals sampled in November 1990. 6 records from Anfibios y reptiles de sistemas cársticos en el municipio de El Peñón, Santander - Proyecto Colombia BIO. 1161 records from (Figure 4) Distribution chart of benthic foraminifers in ODP Site 126-791. 11428 records from Communautés adventices des systèmes cotonniers du nord Cameroun. 13886 records from Données de l'association Nature 18 - Données faune Nature 18 - 2017. 6060 records from Natural History Museum, Vienna - Herbarium W. 104 records from BIRDRACE Die Vriesischen Feigen-Vögel (VFV). 281250 records from Quadrige. 60 records from Phytoplankton abundance measured in surface water during VALDIVIA cruise VA137. 8851 records from Odonata records from RSPB Reserves 1970-2009. 160 records from Inventaires et suivis sites "Espaces Naturels Sensibles" gérés par le Conseil Départemental des Landes - Inventaire "Espaces Naturels Sensibles" de Bas-Rouge (SAINT-MICHEL-ESCALUS). 863 records from Données supplémentaires Atlas des Mammifères marins. 1019 records from Suivi des oiseaux de passage : programme ACT - Programme ACT : Répartition Grive musicienne 2005 - 2009 Coordonnées GPS Lambert 93. 53 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du/de la naturaliste Dubois Yves provenant de la base de donnée du SINP Île-de-France CETTIA. 1962 records from SILENE-FAUNE-PACA - DREAL_PACA_-_N2000_-_Parc_Naturel_Régional_du_Verdon_2017_12_18. 86 records from Occurrence of mammalia relicts at site Bocksteinschmiede. 30 records from Feral Pigs - Sightings and Cull records - 2014-2015. 950 records from Plasm bearing foraminifera counts from multinet SO119_MSN1295. 18 records from Anfibios presentes en el Cerro Jánano. 120 records from Données espèces - Expertise IPE 79. 185 records from Abundance of radiolaria at station UT99-23-2. 1715184 records from NBIS Records to December 2016. 1426 records from SPC PROCFish/C Invertebrates Observations Kiribati 2004. 305 records from Rohrmeistereiplateau und angrenzendes Gebiet. 238 records from (Table 1.2.1.1) Abundance of sympagic meiofauna of sea-ice core PS69/574-1. 24 records from Happywhale - Risso's Dolphin in North Atlantic Ocean. 3481 records from Survey and monitoring records for Scottish Wildlife Trust reserves from reserve convenors and Trust volunteers - Unassessed data. 63 records from Cetacean coordinated transborder monitoring using ferries as platforms of observation off Tunisia 2013-2014 - Atutax. 2510 records from Kenya Wildlife Service, Laikipia Samburu Aerial Census, 2012. 183 records from Marine phytal Harpacticoida from Kenya with emphasis on seagrass dwelling species. 249 records from Projet éolien dit du Château - Données écologiques du projet éolien du Château. 909 records from South American Antarctic Marine Biodiversity Literature. 1 records from Arizona State University Vascular Plant Herbarium. 189 records from Chas.H. O'Donoghue, D.Sc. & Dora de Watteville,M.A. The fishery grounds near Alexandria. XX-Bryozoa. Notes and Memoirs No 34. Hydrobiology and Fisheries Directorate, Egypt.. 14476 records from A grid database on vascular plant distribution in the Meshchersky National Park, Ryazan Oblast, Russia. 81 records from SILENE-FAUNE-PACA - Métropole_Nice_Côte_d'Azur_2017_12_18. 231722 records from Biotope cadastre of the open landscapes, Recorder-Lux database. 1496 records from Stoneworts in Wales. 36 records from City of Edinburgh Natural Heritage Service - Large Red Damselfly Survey. 85 records from Frohlinder Mühlenbach (Dortmund-Kirchlinde). 308 records from Naturmiljø Bergensbanen 2015 (project number 616033). 87 records from Données espèces - Expertise IPE 70. 1028 records from NOAA coral reef monitoring invertebrate data from sites across Micronesia from 2009-09-29 to 2015-09-25. 48 records from FERME ÉOLIENNE DE BLANZAY - Avifaune Blanzay migpost 2016. 1984 records from (Figure 5) Range chart of selected dinocysts and acritarchs of ODP Hole 104-642A. 1114 records from Chronicle of Nature - Phenology of Plants of Kronotsky Federal Nature Biosphere Reserve. 3618 records from Fonoteca Zoológica, Museo Nacional de Ciencias Naturales, Madrid: FZ_AMPHIBIA. 2536 records from Invasive Alien Species Occurrence in Ghana. 63364 records from CCAMLR historic KRILL. 108 records from NEFSC Deepwater Marine Mammal 2002. 240 records from Quarrendorfer Landschaftsschutzgebiet. 168 records from Registros de quirópteros de tres localidades del caribe colombiano. 124 records from Birdrace-Die_Ackermännchen-Schalm-Eder-Kreis. 9982 records from EDP Foz-Tua: Large Mammals (diurnal transects): Ecological Monitoring Program [2011-2017]. 139 records from Réseau Loup - Lynx ONCFS - Lynx 2009 présence Occasionnelle Mailles_10km_LAEA Réseau Loup-Lynx ONCFS. 137 records from Plan régional d'actions en faveur des odonates (PRAO) : 3ème phase (2017 - 2018) menée par le CEN Aquitaine - Observations faunistiques fortuites réalisées lors de journées de prospections animées par le CEN Aquitaine. 1 records from Happywhale - Antarctic Fur Seal in Indian Ocean. 8 records from Abundant box jellyfish, Chironex sp. (Cnidaria: Cubozoa: Chirodropidae), discovered at depths of over 50 m on western Australian coastal reefs. 17 records from Espèces envahissantes de la Guinée forestière extraites dans la base de données de CRRA Sérédou Macenta, IRAG.. 106 records from Helmintos parásitos de peces dulceacuícolas de cuencas hidrológicas del Centro-Norte de México (Durango). 275 records from Composición florística de áreas degradadas por actividad minera a cielo abierto en el municipio de Condoto-Chocó, como insumo para calcular la biomasa vegetal, 2017. 3 records from Happywhale - Adelie Penguin in Southern Ocean. 240 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de Pauline BALDUCCI. 6990265 records from Swiss National Databank of Vascular Plants. 638413 records from Inventaire de la flore d'Alsace - Données de la flore d’Alsace (SBA). 77 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Suivi naturaliste du Parc du Peuple de l'Herbe. 1022 records from Suivi des oiseaux de passage : programme ACT - Programme ACT : Répartition Merle noir 2000 - 2004. 3 records from MSB Mammal Observations (Arctos). 39 records from HRC CRC Small Vessel-Based Monitoring Surveys October 2009. 56 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du/de la naturaliste Goncalves Cristina provenant de la base de donnée du SINP Île-de-France CETTIA. 2126593 records from RSPB Big Garden Birdwatch winter sightings in the UK in 2009. 105 records from Occurrence of mammalia relicts at site Burghöhle Dietfurt. 10 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de Sophie COHEN. 360 records from Microplankton abundance at Station MARCH-1998-GN36199804610MSB03 in the euphotic zone of the Aegean Sea in March 1998. Part 1 - diatoms. 117 records from Centre d'Estudis Avançats de Blanes. Macròfits Pirineu. 26185 records from Données de Mammifères issues de Baznat. Midi-Pyrénées - Données Mammifères Midi-Pyrénées enregistrées dans BazNat - Lot 1. 14 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/009-2. 2 records from Suivi Cistude d'Europe du Bassin de stockage de Balanos - Données Cistude d'Europe du Bassin de stockage de Balanos. 108 records from Dynamics of coastal eutrophicated ecosystems. (IPMS-PHAEO). 18 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT011_3-CTD39. 215 records from Naturpark Kottenforst-Ville Sammelaktion 15.-19.6.. 2023 records from Composición florística y estructura vegetal de una parcela permanente en un relicto de bosque seco tropical en el Caribe colombiano. 299 records from Regroupement d'études et inventaires - Regroupement de données Oiseaux d'eau. 264 records from Microplankton abundance at Station MARCH-1997-GN36199704601MSB02 in the euphotic zone of the Aegean Sea in spring 1997. Part 1 - diatoms. 748 records from Phenological Center - Birds (Laplandskiy). 1635 records from Microplankton abundance in the euphotic zone of the Aegean Sea in September 1994. 551 records from FPN-EH-AVES - Breeding Distribution of seabirds in Patagonia Argentina coast. 1925 records from Caracterización de la vegetación en una zona delimitada en Cumbitara, La Llanada, Policarpa y Los Andes Sotomayor (Nariño), como insumo para la identificación de oportunidades de conservación para la recuperación de los servicios ecosistémicos de bosque seco. 57 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Inventaire faune flore de l'étang d'Abbecourt à Orgeval. 110866 records from Grasshopper and Cricket (Orthoptera) and related species records from Britain and Ireland to 2007. 5 records from Gewässeruntersuchung (Prien) mit Kl. 4b. 998 records from Plant of Folklore (KIDR-PL). 5544 records from Inventaires menés dans le cadre du Groupe Invertébrés de Midi-Pyrénées (GIMP) - Données invertébrés en Midi-Pyrénées. 1019 records from Suivi des oiseaux de passage : programme ACT - Programme ACT : Répartition Caille des blés 2008 - 2012 Coordonnées GPS Lambert 93. 11 records from SNH Invertebrate Site Condition Monitoring of Beetle Assemblage Features 2015: Glen Tarff SSSI. 1142431 records from VegetWeb - Repositorium von Vegetationsaufnahmen. 25 records from Numérisation des données faune contenues dans les Bulletins de la Société Linnéenne de Bordeaux - Bulletin de la Société Linnéenne de Bordeaux, Tome 138 (N.S) n° 31 (1), 2003 - Données faune. 91 records from Zooplancton de sistemas acuáticos artificiales y naturales de Colombia. 27988 records from Bird records for Argyll for the years 2002 and 2003. 4229 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de Loïc SALAUN. 104 records from (Table 2) Palynomorph concentrations in ODP Hole 105-647A samples. 237 records from Virginia CZM Wind Energy Area Survey- Left side - January 2014 through March 2016. 1023 records from Suivi des oiseaux de passage : programme ACT - Programme ACT : Répartition Tourterelle turque 2003 - 2007 Coordonnées GPS Lambert 93. 13871 records from EDP Foz Tua: Terrestrial Birds (transects) - Ecological Monitoring Program [2009-2012]. 1562833 records from Flore Franco-Belge. 1026 records from Suivi des oiseaux de passage : programme ACT - Programme ACT : Répartition Grive littorne 2002 - 2006 Coordonnées GPS Lambert 93. 2507 records from East Ayrshire Species Database. 100 records from Euroants. 1136 records from Phytoplankton abundance in surface water in June 1997, Callao, Peru. 1485 records from (Table 1) Distribution of early late Eocene fossil content in ODP Hole 115-715A. 399 records from Otter (Lutra lutra), Outer Hebrides. 30 records from Ornitofauna de un Área Degradada por Actividad Minera en la Costa Caucana. 6 records from Sarcodine counts and carbon biomass at station TT011_6-CTD71. 9 records from Plan Aquitain d'Action Sonneur à ventre jaune - PRA Sonneur à ventre jaune - étude de répartition. 427 records from Données espèces - Expertise IQE 308. 410 records from Données espèces - Expertise IQE 95. 47 records from Suivi et déplacement d'amphibiens pour la construction de la liaison RD656/RD119 et des carrefours associés (Amorce de la rocade Ouest d'Agen) - Suivi Amphibiens dans le cadre du chantier. 16 records from Estudio herpetofaunístico de la Sierra Mazateca, Oaxaca, México. 4429 records from "Categorization of the wild food plants and their importance for primate development in the natural forest of Akpe (Lama) in southern Benin.". 266 records from Structure of waterbird assemblages in fragmented coastal wetlands of Northeastern Algeria. 26 records from Phytoplankton abundance in surface water in 1994, Ancon, Peru. 1140 records from Plasm bearing foraminifera counts from multinet SO119_MSN1284. 25974 records from Long-term Bird Census in Cigu 2004-2017. 276 records from Aerial Survey Baseline Monitoring in the Continental Shelf Region of the VACAPES OPAREA: January 2016 - December 2016 (right side). 24310 records from Species monitoring and inventories SICONA, Recorder-Lux database. 2079 records from (Table 3B) Occurrence and estimated abundance of planktonic foraminifers at DSDP Holes 85-572C and 85-572D. 710 records from Abundance of living coccolithophores in the northern Arabian Sea (Table 2). 95 records from Projet d'extension de carrière et de mise en place d'une unité de concassage de produits minéraux - Pierrefonds - Saint-Pierre (974) - Inventaires Flore. 339217 records from Carabidae records for Britain to 2014. 1 records from Parc éolien d'Argillières - hérpétofaune. 50 records from Información morfo métrica y de peso de las tortugas acuáticas y los crocodílidos de la Reserva Natural Bojonawi (Vichada) en la temporada de aguas altas. 240 records from SILENE-FAUNE-PACA - BARTH-Environnement_2017_12_18. 8615 records from CSIRO, Tropical Zooplankton Biomass and Composition, Albatross Bay - Gulf of Carpentaria, North Australia 1986-1988. 367 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données arachnologiques de HACALA Axel. 210 records from Microzooplankton abundance measured on water bottle samples at station PS65/514-2. 24 records from SNH Invertebrate Site Condition Monitoring 2013/14: Dollar Glen SSSI. 1140 records from Plasm bearing foraminifera counts of multinet M36/6_MSN1193. 912 records from Total foraminifera counts of multinet M21/2_MSN658. 109 records from MMFR Zingiberaceae Botanical. 45872 records from The national database for marine data (MADS). 1019 records from Suivi des oiseaux de passage : programme ACT - Programme ACT : Répartition Pigeon colombin 2008 - 2012 Coordonnées GPS Lambert 93. 9 records from Microzooplankton abundance and biomass at station TT043_11-1. 2660 records from Patrols activities and fixed transect data collections of the fauna of the W biosphere reserve of Benin of 2017. 19 records from Description of lithologic section units of IODP Hole 325-M0035A. 6 records from Saisie de données naturalistes d'observateurs indépendants sur la plateforme de l'Observatoire FAUNA - Données naturalistes de Kevin CURTIL. 11 records from Prospección de náyades y larvas de odonatos en las cuencas de Urumea, Urola, Deba, Artibai e Ibaizabal - Sistema de Información de la Naturaleza de Euskadi. 101 records from BIRDRACE Enger am Spektiv. 280 records from Size of planktic foraminifera at CTD station M39/4_402CTD-55. 15392 records from Datos de monitoreo de la estructura de los manglares de la Ciénaga Grande de Santa Marta (Magdalena). 1140 records from Total foraminifera counts from multinet M32/3_MSN956. 148 records from Construction du village Alzheimer à Dax (40) - Inventaire de la Faune patrimoniale. 6175 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de Julien BIRARD [Inventaire Eclair 18 juin]. 10 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de CLERGET sylvie. 20 records from Life Vison d'Europe et espèces associées - Données de Vison d'Europe par piège-photo, capture ou indices indirects (empreintes...). 3083 records from Regroupement de données "papillons menacés" collectées par les réseaux entre 1990 et 2012. 1356 records from Programme LIFE CROAA - Eradication de la Grenouille taureau : Piégeage. 217 records from Saisie de données naturalistes d'observateurs indépendants sur la plateforme de l'Observatoire FAUNA - Données naturalistes de Anaelle WILLER. 13 records from Warnowufer Groß Klein. 7 records from Stadtrandlandschaft Apolda-Nord. 63 records from A checklist of amphibians at Lubuk Semilang Recreational Park, Langkawi Island, Kedah, Peninsular Malaysia. 3 records from Microzooplankton abundance and biomass at station NBP97-03-13-2. 9827 records from Meetnetten.be - Population counts for dragonflies in Flanders, Belgium. 34 records from Echinoderms occurence in a strongly contaminated Bay (Portman, Spain), using ROV and Scuba-diving surveys. 165 records from (Table 4) Distribution of calcareous nannofossils at ODP Hole 125-785A. 1628 records from Actualización del conocimiento de la diversidad de especies de invertebrados marinos bentónicos de aguas someras (<50m) del Sur del Golfo de México. 23562 records from Arctic Species Trend Index (ASTI) : Marine. 1007 records from Missisquoi National Wildlife Refuge Bumblebee (Bombus) Surveys. 424 records from Expertise dans le cadre d'une sollicitation liée à une étude d'impact - Données études d'impact CEN M-P. 180 records from Saisie de données naturalistes d'observateurs indépendants sur la plateforme de l'Observatoire FAUNA - Données naturalistes de Dylan FOURNIER. 33415 records from Wolli Creek Preservation Society Bird Survey. 8 records from Abundance and carbon biomass of phytoplankton at station TT007_9-CTD113. 1593 records from The Lichen Flora of Serra de São Mamede Natural Park. 145 records from Biodiversity survey of Rugezi wetland, Year 2013. 63 records from Inventaire des espèces végétales de la vallée de Gounti Yéna (Niamey). 770 records from Waterbird observations in Lake Victoria wetlands, south Kenya coast and Tana River dams (Kenya) in 1995. 449 records from Artsprosjekt Pyrenomycetes. 150 records from Projet de transport par câble entre le Chaudron, Moufia et Bois de Nèfles - Oiseaux - inventaires. 121 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Etude écologique du Parc des Lilas (94). 2890 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données bibliographiques AsFrA. 125 records from Naturschutzgebiet Müchelholz (Mücheln). 11 records from Microzooplankton abundance and biomass at station TT043_27-1. 10 records from PRESENCIA DE VISÓN AMERICANO EN TIERRA DEL FUEGO, MAGALLANES, CHILE. 163 records from Wiese am Waldrand (Gurtweil). 2421 records from Managing open habitats for species conservation: the role of wild ungulate grazing, small-scale disturbances, and scale - Tanacetum vulgare dominated forb vegetation. 5061 records from (Table 2) Distribution of late Miocene to Pleistocene calcareous nannofossils in ODP Hole 105-646B. 403 records from NMML Gulf of Alaska marine mammal survey 2003. 107 records from Veille écologique - Suivi des papillons de jour. 684 records from Plasm bearing foraminifera counts of multinet M12/3_MSN535. 180 records from (Table 2.2.1.1) Abundance of sympagic meiofauna of sea-ice core IO-5. 11840 records from Coral Reef Evaluation and Monitoring Project Florida Keys 2018. 118 records from Birdrace-Birding_Bentheim-Grafschaft_Bentheim. 173 records from Renaturierung Werse (Innenbereich Beckum). 279 records from Atlas des Hyménoptères Pompilidae du Massif armoricain et des départements voisins : prospections 2018. 7 records from Happywhale - Leatherback Sea Turtle in North Pacific Ocean. 700 records from Transfert de fichier de données naturalistes d'observateurs indépendants à l'Observatoire FAUNA - Données naturalistes de Béatrice DELEPINE. 14069 records from Midden-Limburg Fish Ponds Survey. 40 records from (Supplement Table 3) Percentage cover abundance of plants recorded at the Fell-field Site on Disko Island. 252 records from Demande de renouvellement et d'extension d'autorisation de carrière au titre de la rubrique 2510 des ICPE - Carrière de Villemanoche (89) - Donnees biodiversite carriere Villemanoche 181210. 6478 records from National System of Protected Areas in Poland - Animals. 117 records from Зимние маршрутные учеты в заказнике «Березовский» (Ханты-Мансийский Автономный Округ). 325 records from Plan de gestion 2016 - 2020 du site du vallon du Clamondé (64) mené par le CEN Nouvelle-Aquitaine - Observations faunistiques (inventaire) réalisées par le CEN Aquitaine. 26 records from Occurrence of mammalia relicts at site Rusenschloß. 12156 records from WADFW PSAMP S1992. 1819 records from AMAPPS Northeast Aerial Cruise Summer 2016. 11 records from Kenai National Wildlife Refuge, Alaska (KNWR) Fish observations (Arctos). 902 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Geometridae de France métropolitaine. 1140 records from Plasm bearing foraminifera counts of multinet M21/5_MSN730. 4986 records from Photographs of higher plants, mosses, fungi, lichens, and algae. 238 records from Vegetación asociada a la ciénaga de Bete, municipio del Medio Atrato, Chocó 2008. 912 records from Plasm bearing foraminifera counts of multinet POS247/2_MSN1381. 1640 records from (Figure 3) Stratigraphic distribution of planktonic foraminifera in the Neogene of ODP Hole 122-761B. 280 records from Planktic foraminifera counts at CTD station PS55/063. 2144 records from SPC CoFish Invertebrates Observations Marshall Islands 2007. 445 records from South Lanarkshire peatland records 2013. 529 records from NEFSC Mid-Atlantic Marine Mammal Abundance Survey 2004. 16678 records from Suivi Temporel des Libellules (STELI). 83 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du/de la naturaliste GAUTHIER Nicolas provenant de la base de donnée du SINP Île-de-France CETTIA. 168 records from (Table 6) Ranges of benthic foraminifers through the Oligocene in DSDP Hole 22-216. 1653 records from Derbyshire Casual LEPIDOPTERA records - Casual records collated by Derby Museum.. 690 records from Transferts SI Faune - Données naturalistes opportunistes de Cedric DEVILLEGER. 2712345 records from First Bird Atlas. 817 records from Sampling event dataset of Shasha Forest Reserve, Osun State, Nigeria. 1139 records from RV Investigator Voyage IN2017_V02 Seabird Observations, Australia (2017). 1905 records from MMS Marine Mammal Survey, PNW 1989-1990. 487 records from Field Museum of Natural History (Action) Mammals Sightings. 1383 records from Plant observations from Białowieża National Park. 99 records from Inventaires et suivis programme Lagunes mené par le Département des Landes - Ensemble des données Orthoptères. 13442 records from United Kingdom National Whale Stranding Database 1913-2008. 36814 records from Transfert de fichier de données naturalistes d'observateurs indépendants à l'Observatoire FAUNA - Données naturalistes de Christophe CHAMBOLLE. 10385 records from Inventaire de la flore de Charente-Maritime 2012-2020 - Inventaire de la flore de Charente-Maritime 2018. 3939 records from Census of plant species in Pahou forest reserve. 274 records from Agrarian stands of Irvingia gabonensis Aubry-Lecomte ex O'Rorke) Baill. in the department of Couffo in South Benin (West Africa). 79 records from Chronicle of Nature - Phenology of Insects of Tigirek State Nature Reserve. 11 records from Saisie de données naturalistes d'observateurs indépendants sur la plateforme de l'Observatoire FAUNA - Données naturalistes de Laurent ROUSSERIE. 368 records from Lillachtal mit Kalktuffquelle bei Weißenohe. 15 records from Lepidurus arcticus survey Northeast Greenland 2013. 12496 records from Phytoplankton long-term time-series at the fixed coastal station in the Gulf of Naples, data for the years 1984-1991. Part 2. 2808 records from Base BOMBINA du Parc Naturel régional Lorraine - Natura 2000 Vallée de la Seille. 10894 records from Occurrences of the invasive plant species Heracleum sosnowskyi Manden. in the Komi Republic territory (European North-East Russia). 444 records from Phytoplankton abundance at stations off Punta Falsa in August 1995, Piura, Peru. 5 records from Plan de gestion 2007 - 2011 du site des tourbières de Mées (40) mené par le CEN Aquitaine - Observations faunistiques (inventaire) réalisées par le CEN Aquitaine. 197 records from Relative abundance of T. quinqueloba in sediment core PS1243-1. 43066 records from NEOTROPICMYXO. A database of Myxomycetes from the Neotropics. 35 records from Ortsrand Zandershagen. 42 records from An der Weida zwischen Talsperre Zeulenroda und Vorsperre Weida. 44 records from Plan de gestion 2011 - 2015 du site du domaine de Rodié (47) mené par le CEN Aquitaine - Observations faunistiques (inventaire) réalisées par le CEN Aquitaine. 912 records from Plasm bearing foraminifera counts of multinet POS247/2_MSN1384. 2 records from Happywhale - Southern Right Whale Dolphin in South Atlantic Ocean. 1 records from Occurrence of mammalia relicts at site Ballybetagh. 1188 records from (Figure 10) Stratigraphic ranges of selected planktonic foraminifers at ODP Hole 101-631A. 713 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Inventaire entomologique 2020 de la réserve biologique dirigée du Nord Grande Terre, Guadeloupe (ONF). 25446 records from Akita Prefectural Museum, Observation Records of Birds in Akita Prefecture. 98 records from Projet éolien de Berceronne - Données brutes Chiroptères. 505 records from National Frog Survey of Ireland 2010/2011. 31 records from HRC SCC Vessel-Based Monitoring Surveys February 2010. 154 records from HRC USWEX Aerial-based Shoreline Surveys February and March 2011. 585 records from Chronicle of Nature - Phenology of Insects of State Nature Reserve Kivach. 747 records from Vascular plants occurrences in Dokdo islands, Korea, based on herbarium collections and legacy botanical literature. 34 records from Happywhale - Bryde's whale in South Atlantic Ocean. 794 records from USWTR JAX Aerial Survey -Right side- 2009-2010. 338 records from Chronicle of Nature - Phenology of Plants of State Nature Reserve Privolzhskaya Lesostep. 529 records from Registros de dípteros asociados al proyecto: Estratificación espacial del dengue basado en la identificación de factores de riesgo en el departamento del Cauca. 912 records from Total foraminifera counts from M35/1_MSN1065. 45 records from Etat des lieux des suivis effectués dans le cadre de la LGV SEA - Suivi Castor. 452 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Inventaire naturaliste de la commune de Papaichton (Guyane) : mission 2018. 2781 records from Marine Turtles. 7938 records from The Fungal Literature-based Occurrence Database for the Southern West Siberia (Russia ). 32 records from Inventaire Chiroptères sur le site du Roc Branlant - Inventaire et suivi Chiroptères. 178 records from Données du Sanctuaire AGOA issues de l'agence de Aires marines protégées - Données de Mammifères marins. Mission Sanctuaire AGOA de 2012 à 2014. 852 records from Waarneming.nl (NL) - Great Grey Shrike Count 2009-2010. 240 records from Evaluación del macrobentos de la plataforma continental del Caribe colombiano. 374 records from MBON POLE TO POLE: ROCKY SHORE BIODIVERSITY OF GORGONA ISLAND. 2962 records from Alterra (NL) - Microarthropods inventory in calcareous grasslands. 36 records from Animation technique des sites Natura 2000 ‘Barthes de l'Adour’ - Suivis rapaces 2019 - Site Natura 2000 des Barthes de l'Adour. 1020 records from Suivi des oiseaux de passage : programme ACT - Programme ACT : Répartition Tourterelle des bois 2011 - 2015 Coordonnées GPS Lambert 93. 760 records from Total foraminifera counts of multinet M21/2_MSN650. 499 records from Chronicle of Nature - Phenology of Birds of Central Forest State Nature Biosphere Reserve. 5 records from Microzooplankton abundance and biomass at station NBP97-03-03-5. 1745 records from Plan régional d’actions en faveur des lépidoptères patrimoniaux (PRAL) : 1ère phase (2017 - 2018) menée par le CEN Aquitaine - Observations de papillons de jour réalisées lors de journées de prospections animées par le CEN Aquitaine. 1 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de JORIGNE Bastien. 874 records from Total foraminifera counts from multinet M31/3_MSN915. 500002 records from NatureServe Network Species Occurrence Data. 41676 records from Tagged Seal Location Data from SOGLOBEC. 1 records from (Table 1) Concentration of PCB and other contaminants in blood plasma of polar bears (Ursus maritimus) from Svalbard. 12 records from Majidae crabs from Morrocoy National Park - Venezuela. 418 records from Surveys of the East Coast Akalat, Sheppardia gunningi, in Arabuko-Sokoke Forest, 2005-2011. 333 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de Renaud PUISSAUVE. 310556 records from Dry Tortugas Reef Visual Census 2010. 532 records from Global Register of Introduced and Invasive Species - Alaska, United States. 1013 records from Transfert de fichier de données naturalistes d'observateurs indépendants à l'Observatoire FAUNA - Données naturalistes de Stanislas WROZA. 527 records from Observations Faune Flore dans la Réserve nationale de l’Étang de Saint-Paul collectées dans le cadre d'études ou de stages - Suivi ornithologique par IPA et IKA réalisés dans la Réserve nationale de l’Étang de Saint-Paul en 2012 et 2014. 26 records from Cetaceans sighted off the west coast of the South Island, New Zealand, Summer 1970. 182 records from Re-examination of the reef corals of Cocos (Keeling) Atoll, Charlie Veron. 1709 records from The Gibson spider collection. 42 records from ONCFS Réseau Ours brun - Ours 2008 présence Régulière Mailles_10km_LAEA Réseau Ours brun ONCFS. 99 records from Naturgrundstück (Eutin). 193 records from Truppenübungsplatz Panzerkaserne Böblingen. 2385 records from Stratigraphic distribution of marine palynomorph species recorded for the Miocene of ODP Hole 105-645E (Table 1). 651 records from Base BOMBINA du Parc Naturel régional Lorraine - Réseaux écologiques/Trame verte et bleue. 124670 records from Grassland cartography MECDD, Recorder-Lux database. 1 records from Happywhale - Harp Seal in North Pacific Ocean. 229 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données arachnologiques de LEENKNEGT Virginie. 66164 records from Florida Keys Reef Visual Census 1996. 4 records from 1ère phase d'animation (2017 - 2020) des Documents d’objectifs des sites Natura 2000 FR7200665 "Coteaux calcaires de Proissans, Sainte-Nathalène et Saint-Vincent-le-Paluel", FR7200672 "Coteaux calcaires du Causse de Daglan et de la Vallée du Céou" et FR7200676 "Coteaux calcaires de Borrèze" (24) menée par le CEN Nouvelle-Aquitaine - Observations faunistiques fortuites réalisées par le CEN Aquitaine. 574 records from Regroupement d'études et d'inventaires - Données faunistiques en attente de rattachement. 8007 records from Segunda caracterización biológica de aves del proyecto "Incorporación de la Biodiversidad en el sector cafetero en Colombia". 68952 records from Données de la plateforme régionale SINP DREAL Bourgogne - Données de l'Observatoire de la Faune de Bourgogne. 10 records from Projet de centrale photovoltaïque au sol de la ZA de l'Etang Bertrand - Chauves-souris - Points d'écoute au sol. 1022 records from Suivi des oiseaux de passage : programme ACT - Programme ACT : Répartition Perdrix rouge 2009 - 2013 Coordonnées GPS Lambert 93. 12 records from Regroupement d'études et inventaires - Régulation espèces invasives. 1930 records from Fungi of parks, forests and reserves of New Jersey, 2018. 75843 records from Wild bees of Belgium. 18 records from Plan de gestion 2017 - 2021 du site des neuf fontaines et de l'airial du Larousse (40) mené par le CEN Nouvelle-Aquitaine - Observations faunistiques fortuites réalisées par le CEN Aquitaine. 22 records from Observations de tortues marines dans l'archipel de Saint-Pierre et Miquelon. 55 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du/de la naturaliste Villalta Rémi provenant de la base de donnée du SINP Île-de-France CETTIA. 539 records from Phenological Center - Birds (Murmansk). 396 records from Hawthorne Canal Birdwatching Survey. 64 records from Mammals of the Natural Laboratory of Peat-Swamp Forest, Sebangau, Central Kalimantan, Indonesia. 756 records from Mokihinui and Karamaea small tributaries and seeps. 6757 records from Anillamiento de Aves Sierra Nevada de Santa Marta - Proyecto Cruzando el Caribe. 12 records from Sarcodine counts and carbon biomass at station TT012_5-PMOC5. 28 records from Aspilanta new genus (Heliozelidae) specimen data. 117 records from Echinoderms from the Seaflower Biosphere Reserve. 1036 records from Suivi des oiseaux de passage : programme ACT - Programme ACT : Répartition Alouette lulu 1996 - 2000 Coordonnées GPS Lambert 93. 558 records from SILENE-FAUNE-PACA - If_Ecologie_Conseil_2017_12_18. 229 records from Some zoological observations in Kherson region of Ukraine. 5810 records from Grassland cartography SICONA, Recorder-Lux database. 915 records from Rescate de epífitas Oleoducto Bicentenario, Tramo Araguaney - Banadía (rescate). 304 records from (Table 1) Calcareous nannofossil distribution and relative abundance in ODP Hole 114-699A. 368 records from Biological Recording in Scotland - Bumblebee Survey. 304 records from Total foraminifera counts of multinet M6/7_MSN140. 421 records from Monitoreo biológico en la cuenca La Paila, campaña ARA - RARE - CVC – Asociación Calidris. 32 records from MVZ Herp Observations (Arctos). 13 records from Occurrence of mammalia relicts at site Großes Schulerloch. 245 records from Herrensee-Gebiet (Fischbachtal im Odenwald). 205 records from CRC HRC Shore-based Surveys KB11 2013-2015. 11 records from Plan de gestion 2013 - 2018 du site du coteau de Lembeye (64) mené par le CEN Aquitaine - Observations faunistiques fortuites réalisées par le CEN Aquitaine. 4166 records from Línea base general de hormigas para el valle medio del Magdalena - VMM. 6 records from Plan de gestion 2017 - 2021 du site des neuf fontaines et de l'airial du Larousse (40) mené par le CEN Nouvelle-Aquitaine - Observations faunistiques (suivi par dénombrement) réalisées par le CEN Aquitaine. 93 records from Bibliographie de la faune, la flore et la fonge de France métropolitaine et outre-mer - Journal of Hymenoptera Research. 5940 records from Plan Aménagement et de Gestion Simplifié (PAGS) des forêts galeries des départements de l'Ouémé-Plateau. Data mobilized in the framework of a JRS Biodiversity Foundation project in Benin. 528 records from Phytoplankton abundance in surface water in January 1996, Chimbote, Peru. 25 records from Inventario de Murciélagos Buenos Aires, Tauramena, Casanare. 3 records from Saisie de données naturalistes d'observateurs indépendants sur la plateforme de l'Observatoire FAUNA - Données naturalistes de Séverine VITRAT. 1036 records from Numérisation des données faune contenues dans les Bulletins de la Société Linnéenne de Bordeaux - Bulletin de la Société Linnéenne de Bordeaux, Tome 143 (N.S) n° 36 (1), 2008 - Données faune. 30 records from Plan de gestion 2013 - 2018 du site du Coteau de Peymourel (24) mené par le CEN Aquitaine - Observations faunistiques (inventaire) réalisées par le CEN Aquitaine. 1230 records from (Table 2) Distribution of Cretaceous nannofossils at DSDP Hole 79-545. 238 records from Evaluación del ámbito hogareño y calidad de hábitat del borrego cimarrón (Ovis canadensis mexicana), Berrendo sonorense (Antilocapra americana sonoriensis) y del Puma (Felis concolor) en la Reserva de la Biósfera El Pinacate y Gran Desierto de Altar. 44051 records from Alterra (NL) - Entomofauna inventory in peat swamps. 322193 records from Florida Keys Reef Visual Census 2010. 44 records from Bryde’s whales off eastern Venezuela - Aerial 1978-1979. 3040 records from Pollen data of trap CB4. 3 records from Nano and microzooplankton abundance and biomass at station NBP96-04A-11-5. 1140 records from Total foraminifera counts of multinet POS247/2_MSN1377. 1016 records from Suivi des oiseaux de passage : programme ACT - Programme ACT : Répartition Caille des blés 2012 - 2016 Coordonnées GPS Lambert 93. 106 records from Rare vascular plant species in North-West of Kostroma region, Russia. 137 records from Draubiotop Lavamünd. 69 records from Phytoplankton abundance at station Rigel_5_2005-02 in Febraury 2005, Chipana, Chile. 71 records from Plan de gestion 2015 - 2019 du site du Coteau de Monco (33) mené par le CEN Aquitaine - Observations faunistiques (inventaire) réalisées par le CEN Aquitaine. 14 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de LESSIEUR David. 440 records from Large protozoan and small metazoan abundance measured on concentrated water bottle samples at station PS65/593-14. 23217 records from Species inventories NP Öewersauer, Recorder-Lux Database. 360 records from Abundance of planktic foraminifera at CTD station PS55/080-1. 184 records from Foraminifera species abundances from tow TT011_12-MOC74. 192 records from "Schwarzwassertal" bei Pobershau. 27 records from Monitoreo de mastofauna en corredores biológicos de Chiapas. 1 records from Plan de gestion 2016 - 2020 du site des Landes humides de Mouguerre (64) mené par le CEN Nouvelle-Aquitaine - Observations faunistiques fortuites réalisées par le CEN Nouvelle-Aquitaine. 20 records from Occurrence of mammalia relicts at site Bivak Cave. 310 records from GNOR-Projekt "Halbwilde Weidehaltung zwischen Kamp-Bornhofen und Kestert" und Umland. 10 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de DURON Cyril. 960 records from Microplankton abundance at Station SEPT-1997-GN36199704605MSB02 in the euphotic zone of the Aegean Sea in September 1997. Part 2 - dinoflagellates. 41552 records from Staffordshire Wildlife Trust Nature Reserves Inventory. 1 records from Happywhale - Black Dolphin in South Atlantic Ocean. 2225 records from Northern Territory WildWatch. 11 records from NMML Harbor Porpoise Aerial Survey, Cook Inlet, 1991. 40 records from Elaboration du DOCOB du site Natura 2000 ‘Marais du Bas Médoc’ (FR7200680) - Inventaire Faune. 24 records from Plan de gestion 2006 - 2010 du site du site du domaine de Rodié (47) mené par le CEN Aquitaine - Observations faunistiques (inventaire) réalisées par le CEN Aquitaine. 208 records from Registros de arañas en el marco del proyecto Influencia de la dieta sobre la toxinología y toxicología en arañas. 214 records from MEMO+ - Monitoring exotic mosquitoes in Belgium. 11840 records from Coral Reef Evaluation and Monitoring Project Florida Keys 2016. 2224 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données de Lépidoptères de Bruno DAUGET - Dépt de l'ALLIER (03). 17827 records from Condition of rocky reef communities around Tasmania: fish surveys, Australia (1992-1995 and 2006-2007). 240 records from Landschaftspflegehof (Berlin). 1553 records from University of Valencia cetacean surveys in the Spanish Mediterranean 2000-2003. 210 records from Numérisation des données faune contenues dans les Bulletins de la Société Linnéenne de Bordeaux - Bulletin de la Société Linnéenne de Bordeaux, Tome 146 (N.S) n° 39 (4), 2011 - Données faune. 9 records from Bachpatenschaft Beeke. 75 records from BIRDRACE Hasenclevers Erben - NaBu-Bi-BirdRace-Open. 242 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - EPTBSGL_ANSE_ARCOT_2019. 462 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du/de la naturaliste Dodelin Benoît provenant de la base de donnée du SINP Île-de-France CETTIA. 64 records from Anfibios y reptiles del páramo de Sumapaz - Proyecto Colombia Bio. 202860 records from TPWD HARC Texas Coastal Fisheries Upper Laguna Madre Gill Net. 44 records from Estado actual, identificación de riesgos y propuestas para el manejo de las especies invasoras presentes en las regiones hidrológicas prioritarias, confluencia de las Huastecas, Media Luna y Cabecera del río de La Laja. 1140 records from Total foraminifera counts from M35/1_MSN1051. 354 records from SPC CoFish Invertebrates Observations Niue 2005. 1498 records from Gemeinde Sursee. 1 records from Plan de gestion 2019 - 2023 de la Réserve Naturelle Régionale des carrières de Tercis-les-Bains (40) mené par le CEN Nouvelle-Aquitaine - Observations faunistiques fortuites réalisées par la RNG Saucats - La Brède. 5366 records from City of Edinburgh Natural Heritage Service - Bavelaw Marsh Bird Hide Records. 1692 records from Evaluación de especies vegetales aptas para la restauración ecológica de una plantación forestal exótica en la localidad de San Cristóbal - Bogotá. 852 records from Données de l'Observatoire des Mammifères marins de l'Archipel Guadeloupéen - Observatoire des Mammifères marins de l'Archipel Guadeloupéen. Suivi Dauphins Les Saintes. 18 records from Occurrence of mammalia relicts at site Nazeing. 569 records from Spatial repartition of Antiaris toxicaria Lesch., Ceiba pentandra (L) Gaert, Terminalia superba Engl. & Diels and Triplochyton scleroxylon K. Schum. in Niaouli, Bonou, Pobe forests (South-Benin). 165 records from Artenvielfalt auf den Elbwiesen (Dessau). 1010 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de Daniel PAVON. 4512 records from Chronicle of Nature - Phenology of Plants of Carpathian Biosphere Reserve. 59 records from Seabird and cetacean sightings from Cruise SY002 of RV Shoyo Maru, Tropical Atlantic Ocean, Oct. 2000. 102 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données de la naturaliste Clélie Granger. 525 records from Flora y fauna asociada al hábitat del Manatí antillano en la Ciénaga de Paredes, Magdalena Medio Santandereano. 1 records from Plan de gestion 2015 - 2019 du site de Pey Landry (33) mené par le CEN Aquitaine - Observations faunistiques fortuites réalisées par le CEN Aquitaine. 90 records from NMML Harbor Porpoise Aerial Survey, Kodiak Island, Replicate 3, 1992. 468 records from Microplankton abundance at Station MARCH-1997-GN36199704601MSB06 in the euphotic zone of the Aegean Sea in spring 1997. Part 2 - dinoflagellates. 37 records from Implantation d'une centrale photovoltaïque au sol à Chacé - Etude écologique. 1140 records from Total foraminifera counts of multinet M21/1_MSN606. 220 records from Inventario de Mamíferos Mámbita. 5 records from Microzooplankton abundance and biomass at station NBP97-08-25-4. 60 records from Caracterización de la fauna reptiliana asociada a la cuenca del río Atrato, para el estudio de su navegabilidad, Quibdó - Chocó, 2012. 269 records from Programme LIFE CROAA - Eradication de la Grenouille taureau : Barrière-piège. 17 records from Feuchtwiese am Nationalpark-Haus Neuwerk. 326086 records from Estonian Nature Observations Database. 189 records from Naturpark Sternberger Seenland. 23 records from 2017 Onwards Rare Invertebrates in the Cairngorms Northern Silver Stiletto Fly Survey Data. 1599 records from Inventaire des bois par espèce végétale de la forêt classée de Ziama en Guinée Forestière (BID-AF2015-0066-REG). 589 records from Birds (NMNO-BI). 798 records from (Table 6) Distribution of planktonic foraminifers in ODP Site 112-684. 3 records from Mise en oeuvre des mesures compensatoires à l'aménagement du parc photovoltaïque d'Hourtin - Données opportunistes. 91 records from Heard Island Shag Phalacrocorax nivalis census, Heard Island 1992. 210 records from Microzooplankton abundance measured on water bottle samples at station PS65/546-2. 3670 records from Aves del Parque Nacional Cumbres de Monterrey, Nuevo León, México. 235 records from Chronicle of Nature - Phenology of Insects of Kaniv Nature Reserve. 90 records from GEO-Tag mit der NAJU des Landkreises Ahrweiler am Bausenberg. 370 records from Microplankton abundance in the euphotic zone of the Aegean Sea in winter 1995. 42 records from 76 - Bois de Beaumont - Chiroptères. 770 records from Nivå Bay species list, Zealand, Denmark. 20 records from Biology and population studies of two endemic orchid species on sub-Antarctic Macquarie Island. 122 records from Inventaires de la Flore Patrimoniale de la Réserve Naturelle Nationale Étang de Saint-Paul - Inventaire de la Flore patrimoniale dans la RNN Etang de Saint-Paul avant le 31/12/2017. 69 records from Fungal Bioblitz in Białowieża Primeval Forest at 18th Congress of European Mycologists. 2025 records from Phytoplankton abundance during HYDROMET cruise Hydromet90/4. 1 records from Regroupement d'études et inventaires - Mortalité lignes HT. 4284 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de Matthias COLIN. 160 records from Seabird sightings in Ghana and Ivorycoast. 216888 records from Species data for Scottish waters held and managed by Scottish Natural Heritage, derived from benthic surveys 1993 to 2018. 71 records from Avifauna asociada al área boscosa del resguardo indígena Cuti, municipio de Unguía, Chocó. 2020. 1140 records from Total foraminifera counts from multinet M31/3_MSN898. 241 records from (Table 1) Distribution of benthic foraminifera in Eocene-Oligocene sediments of DSDP Hole 12-119 in the Bay of Biscay. 6 records from Plan de gestion 2010 - 2014 du site du Coteau de Casserouge (47) mené par le CEN Aquitaine - Observations faunistiques (inventaire) réalisées par le CEN Aquitaine. 34 records from Saisie de données naturalistes d'observateurs indépendants sur la plateforme de l'Observatoire FAUNA - Données naturalistes de François FAURE. 1140 records from Plasm bearing foraminifera counts of multinet M36/2_MSN1107. 324 records from Phytoplankton abundance at station CD46_0705C#4. 272522 records from DFO Pacific Groundfish Synoptic Trawl Surveys - Hecate Strait. 9 records from tranfert des activités ferrovaires du site de Nantes-Etat vers le site de Nantes-Blottereau - Inventaire d’espèces végétales protégés et/ou patrimoniales - Point. 595 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/049-3. 31 records from Registros de mamíferos de los Parques Ecológicos Distritales de Montaña de Bogotá, D.C.. 29 records from Hemmerder Schelk (Unna). 13 records from Atlas des oiseaux nicheurs de France réalisés par carte IGN50 - Données additionnelles d'Echasse blanche Himantopus himantopus 1980-1991 nicheuse probable ou certaine (hors période atlas 1985-1989). 39643 records from Fife Nature Records Centre combined dataset. 798 records from Plan régional d'actions en faveur des odonates (PRAO) : 3ème phase (2017 - 2018) menée par le CEN Aquitaine - Observations d'odonates réalisées lors de journées de prospections animées par la LPO Aquitaine. 1140 records from Total foraminifera counts of multinet M21/1_MSN604. 59 records from Inventaires de la RN d'Arjuzanx - Données opportunistes récoltées lors de missions de terrain des agents. 237 records from Avifauna asociada a humedales urbanos del municipio de Quibdó - Chocó, 2019. 178 records from Parc éolien de la Société d’Exploitation du Parc Eolien des Noues à Blacy (51) - Points d'écoute au sol des chiroptères. 100 records from Plan de gestion 2009 - 2013 du site des Grottes de Sare (64) mené par le CEN Aquitaine - Observations faunistiques (suivi par dénombrement) réalisées par le CEN Aquitaine. 2304 records from Ridge to Reef Marine Monitoring of Fanga'uta Lagoon, Tonga, October 2017. 41 records from Etude préalable au plan de gestion des lagunes d'Hourtin pour la protection des sites à leucorrhines menée entre 2015 et 2019 par le CEN Aquitaine - Observations faunistiques (suivi par point d'écoute) réalisées par le CEN Aquitaine. 1140 records from Plasm bearing foraminifera counts of multinet M21/5_MSN732. 2490 records from Diagnóstico del aprovechamiento de flora y fauna por los mayas del Ejido Petcacab y evaluación de la cacería y pesca, Felipe Carrillo Puerto, Quintana Roo. 117 records from Naturschutzgebiet Lochbusch-Königswiesen. 7 records from Grundwasserlebensraum im Englischen Garten (München). 4 records from Saisie de données naturalistes d'observateurs indépendants sur la plateforme de l'Observatoire FAUNA - Données naturalistes de Joël BRIED. 180 records from (Table 2) Range chart for planktonic foraminifers from ODP Hole 111-677B. 30 records from Invertebrados del Parque Nacional Arrecife Puerto Morelos. 40 records from Seawater carbonate chemistry and boron incorporation of planktic foraminifer Orbulina universa during experiments, 2011. 105 records from Occurrence of mammalia relicts at site Stadel im Hohlenstein. 8 records from The Collection of Lichenicolous Fungi at the Botanische Staatssammlung München. 46 records from Fauna anfibia asociada al bosque del resguardo indígena Cuti, municipio de Unguía, Chocó. 2020. 20495 records from Inventaire de la flore de Charente-Maritime 2012-2020 - Inventaire de la flore de Charente-Maritime 2017. 59 records from Parc photovoltaïque sur la comme de Préfontaines - Parc photovoltaïque sur la commune de Préfontaines. 31 records from Caracterización Ecológica de los Macroinvertebrados de las Fuentes Hídricas presentes en el Cerro Jánano. 468 records from Microplankton abundance at Station MARCH-1997-GN36199704603MNB03 in the euphotic zone of the Aegean Sea in spring 1997. Part 2 - dinoflagellates. 720 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du naturaliste Bussac Augustin provenant de la base de donnée du SINP Île-de-France CETTIA. 26 records from Erhard Sopp. 137 records from Atlas de la biodiversité de Bordeaux Métropole 2015 - Recensement des chiroptères 2012/2014 - Atlas de la biodiversité de Bordeaux Métropole. 4853 records from Inventaire des espèces végétales du sous bois des plantations de Teck de la forêt naturelle de la Lama. 97 records from Dorfrand Mauderode. 260 records from Abundance of planktic foraminifera at CTD station PS55/082-1. 411 records from SuLaMa reptile survey I 2012. 48 records from (Table 2) Abundance of Globigerinoides sacculifer and Globigerinoides ruber and oxygen and carbon stable isotopes of different planktonic foraminifers at DSDP Hole 78-543. 61 records from Shrews of Poland. 181 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du/de la naturaliste Beutin Sabine provenant de la base de donnée du SINP Île-de-France CETTIA. 41029 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de Pascal Dupont. 1504 records from Woodmeadow Invertebrate Survey 2019. 18 records from Système d'Information sur la Nature et les Paysages d'Ile de France - suivi du site Natura 2000 Carrière Saint Nicolas. 91 records from Microzooplankton abundance measured on water bottle samples at station PS58/061-1. 270901 records from TPWD HARC Texas Coastal Fisheries Corpus Christi Bay Bag Seine. 108 records from Monitoreo hidrobiológico en el Río Aures para el tramo de influencia de la central Aures Bajo. 2170 records from Inventaire des sangsues du Nord-Ouest de la France - réalisation d'un guide à destination du grand public et des naturalistes - Inventaire des sangsues - détermination prélèvements de bureau d'études (qualité de l'eau) - Subvention UMS Patrinat. 310 records from Registros de macroinvertebrados acuáticos en un bosque seco del municipio de Honda. 828 records from Phytoplankton abundance in surface water in May 1996, Ilo, Peru. 350 records from (Table 2.2.2.1) Integrated abundance of sympagic meiofauna in sea-ice cores of Aurora Australis cruise SIPEX. 2 records from Wie viel Natur gibt es im Park?. 31 records from STELI 2015 Saint-Pée-sur-Nivelle (64) par l'association EcoGIS. 598 records from Monitoreo de la abundancia, riqueza y biodiversidad de aves del Santuario de Flora y Fauna Galeras en 2019. 181715 records from Marine benthic dataset (version 1) commissioned by UKOOA. 5665 records from The Dolphin Project. 172 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du/de la naturaliste Roquinarc'h Océane provenant de la base de donnée du SINP Île-de-France CETTIA. 4 records from Abundance of microplankton from bottle APRIL-2000-K3. 600 records from Occurrence data of Birds of the Upper Tana Basin, Kenya. 1024 records from Bibliographie de la faune, la flore et la fonge de France métropolitaine et outre-mer - Zootaxa. 1857 records from Inventaire national des Crustacés Décapodes de France métropolitaine - Inventaire des Crustacés Décapodes de France métropolitaine. Données du compte CardObs 1113. 6787 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du naturaliste MIGUET Pierre provenant de la base de donnée du SINP Île-de-France CETTIA. 214 records from Caracterización de vertebrados terrestres en el Cerro Guadalupe, municipio de Manzanares. 14181 records from Index Site Surveys Data for Olympia Oysters, Ostrea lurida, in British Columbia – 2009 to 2017. 410 records from Aves de Caño Cristales, La Macarena, Meta. 661 records from Etude floristique de la forêt marécageuse de Lokoli au Bénin. 3018 records from SPC PROCFish/C Invertebrates Observations Wallis and Futuna 2005. 307 records from Umgebung der Gesamtschule Hamburg-Winterhude. 11131 records from Efectos del Cambio Ambiental en las comunidades de organismos de los ríos mediterráneos. 5 records from Marine algal (seaweed) flora of São Jorge Island, Azores. 2970 records from Distribution patterns of subtidal macrobenthos in the Tsitsikamma National Park. 1024 records from BUND - Dassower See (Lübeck/Dassow). 104 records from (Table 3) Abundance and biomass of Proboscia alata in patches of its mass development over the Bering Sea middle shelf, percentages of P. alata and associated algae species and their groups in total phytoplankton abundance and biomass. 65276 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de Monsieur François FOURNIER. 352 records from Birds and plant species near Petushki town (Vladimir region). 44 records from Mamíferos de la Ecoreserva CPF Cupiagua (Aguazul, Casanare) - Proyecto FIBRAS. 2472 records from Bibliographie de la faune, la flore et la fonge de France métropolitaine et outre-mer - Revues diverses et littérature grise.. 912 records from Phytoplankton abundance in surface water in September 1997, Chimbote, Peru. 1 records from Plan de gestion 2017 - 2021 du site des tourbières de Mées (40) mené par le CEN Nouvelle-Aquitaine - Observations faunistiques (suivi par plaques) réalisées par le CEN Nouvelle-Aquitaine. 531 records from Fish biodiversity of the Vitória-Trindade Seamount Chain, Southwestern Atlantic: an updated database. 9 records from Convention - Fondation d'Entreprise du Golf de Vidauban pour l'Environnement - Jeu de données convention FEGVE-SPN (numéro 2). 4 records from Sächsische Schweiz (Wehlener Gebiet). 4 records from Nano and microzooplankton abundance and biomass at station NBP96-04A-03-16. 84624 records from TPWD HARC Texas Coastal Fisheries Sabine Lake Gill Net. 279 records from Peces asociados a raíces de manglar en el PN Morrocoy, Venezuela. 42 records from SILENE-FAUNE-PACA - DREAL_PACA_-_N2000_-_Pays_Provence_Verte_2017_12_18. 30 records from ONCFS Réseau Ours brun - Ours 2004 présence Occasionnelle Mailles 10km LAEA Réseau Ours brun ONCFS. 126 records from Appendicularia abundance of station M9_A near the Great Meteor Bank, Northeast Atlantic (Table 1). 977 records from Creación de un área protegida pública local en los municipios de Roldanillo, La Unión y Toro.. 2820 records from Surface seawater carbonate chemistry, nutrients and phytoplankton community composition on a transect between North Sea and Arctic Ocean, 2008. 15 records from Plan de gestion 2014 - 2018 de la Réserve Naturelle Régionale des carrières de Tercis-les-Bains (40) mené par le CEN Aquitaine - Observations faunistiques (suivi par piège lumineux) réalisées par le CEN Aquitaine. 50 records from Lindesnes. 570 records from Cuxhavener Küstenheiden. 378 records from (Table 2) Fossil record of foraminifera and ostracoda from Muldsberg clay pit, north Germany. 1991286 records from Hatikka.fi observations. 1289 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de Monsieur JOURDE Rémi. 814 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de AUNEAU Florent. 1019 records from Suivi des oiseaux de passage : programme ACT - Programme ACT : Répartition Geai des chênes 2008 - 2012 Coordonnées GPS Lambert 93. 600 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Accipitridae. 35 records from Occurrence of mammalia relicts at site l´Abri de Campalou. 1280 records from (Table 2) Stratigraphic occurrence of selected diatom species from DSDP Hole 12-112. 1520 records from Total foraminifera counts of multinet M21/6_MSN784. 48 records from (Appendix B) Calcareous benthic foraminifers in ODP Hole 123-765C. 9 records from Inventario Herpetológico Pauto M, La Primavera, Yopal, Casanare. 91 records from Megafauna of the UKSRL exploration contract area and eastern Clarion-Clipperton Zone in the Pacific Ocean: Annelida, Arthropoda, Bryozoa, Chordata, Ctenophora, Mollusca. 62 records from Zoo Frankfurt. 212 records from Estrategia de conservación de grandes felinos en el departamento del Meta. 129 records from BIRDRACE Oostfreesland Bird-Lopers. 238 records from Données de Aquasearch et Dauphin Passion - Données Mammifères marins Aquasearch - Dauphin Passion. 177 records from Canada_BasinMegabenthos2002. 8066 records from Coral Reef Evaluation and Monitoring Project Florida Keys 2009. 1084252 records from Fungal Records Database of Britain and Ireland. 31 records from Bulletin d'informations de l'Association française de Lichénologie. 484765 records from Local floras of Russia: records from literature. 277 records from Norfish: Shetland Cod Fishery 1520-1796. 950 records from Total foraminifera counts of multinet M21/2_MSN643. 237 records from Capercaillie national surveys. 61 records from Ferme éolienne de Saint-Hilaire-du-Maine - Insectes patrimoniaux observés durant les expertises entomologiques en 2014. 356 records from Morphologische Daten von Puffinus creatopus. 505 records from (Table 3) Protist occurrence in bottom sea ice and surface water samples obtained during a CCGS Amundsen cruise in 2007/2008. 830 records from Inventaires et suivis faune - Regroupement de données Odonates et Lepidotères. 23648 records from WTSWW Data: All Taxa (West Wales). 1494 records from EDP Foz Tua Nocturnal Birds - Ecological Monitoring Program [2011-2017]. 7 records from Fichas diagnósticas para 10 especies de anfibios y reptiles mexicanos. 608 records from CRESLI marine mammal observations from whale watch cruises 2000-2019. 2 records from Happywhale - Southern Bottlenose Whale in Southern Ocean. 421246 records from Cartografía de vegetación a escala de detalle 1:10.000 de la masa forestal de Andalucía. 129 records from Données espèces - Expertise IPE 10. 63 records from Marine gastropod distribution from patagonian shallow waters. 96 records from "Ahrschleife bei Altenahr". 150 records from Plan de gestion 2008 - 2012 du site de la Butte de la Lot (33) mené par le CEN Aquitaine - Observations faunistiques (inventaire) réalisées par le CEN Aquitaine. 5681 records from South Australian Museum Australia provider for OZCAM. 912 records from Plasm bearing foraminifera counts from multinet M32/3_MSN957. 69 records from Phytoplankton abundance at station Rigel_4_2005-05 in May 2005, Chipana, Chile. 46 records from Coccolith counts of multinet M32/5_MSN981. 1 records from Occurrence of mammalia relicts at site Stockton-on-Tees. 160 records from (Table 1) Distribution of planktonic foraminifers in ODP Hole 126-787B. 6 records from Sarcodine counts and carbon biomass at station TT008_6-PMOC7. 7208 records from Whicher Scarp Flora Survey. 23 records from Landwehrbach. 105 records from Projet BiodiverCité - Données opportunistes de Frédéric Revers récoltées lors des prospections terrains. 10079 records from CSIRO, fish surveys by the Soela, 1980s. 25 records from Herpetofauna de la expedición Piedemonte Llanero - Proyecto Boyacá BIO UPTC. 62 records from Artenvielfalt in der Kinderakademie im RFZ. 8984 records from Participation aux politiques publiques départementales de l'environnement - Données CEN M-P départements. 61 records from Alien Species in Poland - Plants. 11 records from Inventaires et suivis effectués sur les retenues collinaires de l'Institution Adour - Inventaire sur la retenue collinaire de Renung. 37 records from Diversity of littoral peneid shrimps in Falcon State, Venezuela. 3275 records from Trawl-survey data from the “expedition Hvar” in the Adriatic Sea (Mediterranean) collected in 1948-1949. 402 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données de VINCENT Alexis (SAPROX). 5 records from Happywhale - Sei Whale in North Pacific Ocean. 56 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Alcedinidae. 1162 records from Avifauna de bosques nublados en la cordillera Occidental, departamentos del Valle del Cauca, Risaralda y sur de Antioquia.. 3763 records from Empire Wind Digital Aerial Wildlife Surveys for BOEM Lease Area OCS-A 0520, Equinor Wind US LLC, November 2017-October 2018. 1169 records from Glasgow Museums BRC: Chrysomelidae. 56 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données de la structure Forêts en Aulnoye provenant de la base de donnée du SINP Île-de-France CETTIA. 27 records from Projet de parc éolien en mer des îles d'Yeu et de Noirmoutier - demande de dérogation espèces protégées - Mammifères marins GT - Inventaire non protocolé. 912 records from Total foraminifera counts of multinet M26/1_MSN844. 1140 records from Total foraminifera counts of multinet FCA97C_MSN1339. 4 records from Microplankton abundance at bottle station SEPT-1999-K4. 47 records from Freiheitsring (Frechen). 336 records from Aves de la Ecoreserva La Tribuna (Neiva, Huila) - Proyecto FIBRAS. 1 records from Happywhale - Clymene Dolphin in South Atlantic Ocean. 28 records from Bryde’s whales off eastern Venezuela - Vessel 1978-1979. 273 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/043-4. 492 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station MARCH-94-GN3619940280100500. 1443 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du naturaliste Doux Yves provenant de la base de donnée du SINP Île-de-France CETTIA. 1 records from Synthèse de la Répartition des populations de bouquetin des alpes en 2005 (réseau Ongulés sauvages ONCFS-FNC-FDC). 1462 records from Avifauna en dos parches de bosque seco del departamento del Valle Cauca (Colombia). 3 records from Happywhale - Dusky Dolphin in South Pacific Ocean. 584 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du naturaliste Christian Desmier. 6992 records from Stone-curlew Annual Surveys. 97 records from Avifauna asociada a las fuentes abastecedoras de agua en La sierpe - Osbezcac (rio Saija, Timbiquí - Cauca). 445 records from (Table 14) Distribution of planktonic foraminifers in ODP Hole 108-665A. 829 records from Aves Argentinas / Asociación Ornitológica del Plata - Conteo anual de chorlos de pastizal en Argentina - Campaña enero 2009. 106 records from Occurrence of mammalia relicts at site Geißenklösterle. 261 records from (Table 2) Distribution of Eocene to Paleocene calcareous nannofossils in ODP Hole 114-699A. 1673 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de Bernard Lalanne-Cassou. 11934 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de Franck NOEL. 272 records from Norfish: Norway Cod Fishery 1520-1791. 365 records from Base BOMBINA du Parc Naturel régional Lorraine - Natura 2000 ZPS Jarny - Mars-la-Tour. 1014 records from Suivi des oiseaux de passage : programme ACT - Programme ACT : Répartition Etourneau sansonnet 2006 - 2010 Coordonnées GPS Lambert 93. 36 records from Happywhale - Sperm Whale in South Pacific Ocean. 7 records from Projet de parc éolien de la Croix Guingal, sur la commune de Derval (44 590) - Croix Guingal - Chiro - parturition 2014. 895 records from Avifauna asociada a paisajes rurales degradados en la vereda San Luis, Barrancabermeja - Santander. 622 records from Inventaires Odonatologiques de sites ENS du Pôle Nature de Vitrezay (St Sorlin de Conac) et de St Clément des baleines - Liste odonates 2 sites ENS Charente-Maritime. 3327 records from BioGIS - Mammals - SPNI. 635 records from Carnarvon Basin wetland survey. 2369 records from Chronicle of Nature - Phenology of Birds of Darwin Nature Biosphere Reserve. 511 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Dirección General de Medio Natural y Política Forestal. Inventario Nacional de Biodiversidad 2007, Invertebrados. 29523 records from Données du Parc national des Cévennes - Inventaire et suivis d'espèces dans le Parc national des Cévennes. 3 records from Happywhale - Chinstrap Penguin in Southern Ocean. 53 records from Suivi de l'évolution des populations - Inventaire et suivi Odonate – Protocole STELI. 346 records from Registros biológicos de 5000 árboles sembrados por el Jardín Botánico de San Andrés en las islas de Providencia y Santa Catalina. 933265 records from SEWBReC Birds (South East Wales). 232 records from Luderbusch. 50940 records from NOAA National Coral Reef Monitoring Program Benthic Percent Cover. 82 records from Teich im Wald zwischen Böblingen und Schönaich. 807 records from Monitoreo de aves por medio de puntos de conteo en el Santuario de Flora y Fauna Galeras en 2016. 7606 records from Lepidoptera of Mordovia State Nature Reserve. 2504 records from Collections data on ecology of bottom animal of the Southern ocean. 5695 records from SPC PROCFish/C Fish Observations Vanuatu 2003. 475 records from Peces de las lagunas costeras de Isla Margarita, Venezuela. 912 records from Total foraminifera counts from multinet SO119_MSN1285. 5934 records from Agroforestry species in Parkia biglobosa's parklands in Northern Benin. 119365 records from Isle of Man wildlife records from 01/01/2000 to 13/02/2017. 22 records from The fishery ground near Alexandria. XVI. Cumacea, stomatopoda, leptostraca by Adolf Steuer (1938).Notes and Memoirs No 26.. 47 records from Projet du parc éolien de la Voie des Prêtres 2 - Liste de l'avifaune recensée en hivernage 2010-2011. 625 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données arachnologiques de Corse par Canard A., Rollard C., Villepoux O.. 19780 records from Eulachon migration bottom trawl surveys. 371 records from Projet éolien - Oiseaux - Inventaire non protocolé. 6321 records from Nonindigenous Aquatic Species (NAS) Database Non-freshwater Specimens. 2118 records from Registros biológicos de flora para el desarrollo de acciones de evaluación, seguimiento y monitoreo en los elementos priorizados de la estructura ecológica principal del distrito capital. Bogotá D.C.. 40 records from Occurrence of mammalia relicts at site Zigeunerfels. 170 records from SNH Invertebrate Site Condition Monitoring 2013/14: Eastern Cairngorms SSSI. 9634639 records from Pl@ntNet automatically identified occurrences. 97 records from Base BOMBINA du Parc Naturel régional Lorraine - Amphibiens filet/Marbotte-Ronval 2013. 131935 records from Amphibiens et Reptiles de France (Enquête 2). 5 records from Dolichopodidae of Portugal - dataset 2009-2018. 1405 records from Inventario de la biota marina (cnidarios, poliquetos, moluscos, crustáceos, equinodermos y peces) del Santuario Islas e Islotes de Bahía Chamela, Jalisco, México. 34 records from Expertise dans le cadre d'une sollicitation liée à une étude d'impact - Données GSM Carrière Espeyran. 7326 records from Ravensthorpe Range survey data. 140 records from SNH Invertebrate Site Condition Monitoring 2015: Blind Moss SSSI. 14 records from Contribution à la connaissance des Orthoptères – Locusta - Données opportunistes de Benoit DUHAZE. 912 records from Plasm bearing foraminifera counts of multinet M42/3_MSN1360. 5 records from Schulinnenhöfe (Gelsenkirchen). 157 records from Wirbach-Taubental (Bad Blankenburg). 3537 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes d'Alain BERLY. 1 records from Nano and microzooplankton abundance and biomass at station NBP97-01-13-5. 15 records from Hache im Ellernbruch (Sudweyhe / Weyhe). 1386 records from Regroupement d'études et inventaires - Données opportunistes. 51 records from Nanoplankton abundance at station GeoB2012-5. 1698 records from Red-throated diver national surveys in Scotland - raw data. 1960 records from (Figure 7) Distribution chart of benthic foraminifers in ODP Site 126-793. 368 records from Ring ouzel national sample survey in the UK in 1999. 37 records from City of Edinburgh Natural Heritage Service - Harperrig Otter Survey. 841 records from Dorset Invasive Alien Plants - NBN South West Pilot Project Case Studies. 7490 records from SILENE-FAUNE-PACA - Yoann_BLANCHON_2017_12_18. 324 records from Transfert de fichier de données naturalistes d'observateurs indépendants à l'Observatoire FAUNA - Données naturalistes de Marc CORAIL. 255 records from Elaboration du DOCOB du site Natura 2000 ’Réseau hydrographique du Midou et du Ludon’ (FR7200806) - Inventaire et regroupement de données Natura 2000. 12865 records from Données bibliographiques et opportunistes Mammifères du Nord Pas-de-Calais issues du SIRF. 33 records from Seguimiento y actualización de la distribución y abundancia de sábalo (Alosa alosa L.) y lamprea (Petromyzon marinus L.) en el País Vasco - Sistema de Información de la Naturaleza de Euskadi. 13 records from Réseau Loup - Lynx ONCFS - Réseau Loup-Lynx : Répartition communale Régulière du Loup en 1997. 266 records from PARC PHOTOVOLTAIQUE à RIANS - Flore. 146 records from Abundance of birds in the Lena Delta Region. 1022 records from Suivi des oiseaux de passage : programme ACT - Programme ACT : Répartition Alouette lulu 2009 - 2013 Coordonnées GPS Lambert 93. 125 records from Succession of benthic hard-bottom communities abundance at station Errina2012_CS. 165 records from Transcription of selected miombo timber species of a floristic inventory in Cuando-Cubango, Angola. 6525 records from Phytoplankton abundance during Arnold Veimer cruise AV90/2. 1 records from Synthèse de la Répartition des populations de chamois en 1988 (réseau Ongulés sauvages ONCFS-FNC-FDC). 124 records from Kirkliston Range stream monitoring. 60 records from Amtsrain Apolda-Zottelstedt. 96 records from Phytoplankton abundance measured on water bottle samples during Jan Mayen cruise JM1. 130 records from Atlas communaux de la Biodiversité du Parc Naturel Régional des Landes de Gascogne (PNRLG) - Inventaire des reptiles 2014. 16 records from PROJET DE CONSTRUCTION D’UNE ROUTE DE TRANSPORT DES MINERAIS DE BAUXITE DE GAC: EIES, inventaire des amphibiens (CESP2016-022). 40135 records from DIBA-Parc del Montnegre i el Corredor. 4764 records from USGS ASC - Yukon Kuskokwim River Delta - Birds - 1992-2002. 196 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du/de la naturaliste LELARDOUX LOIC provenant de la base de donnée du SINP Île-de-France CETTIA. 583 records from MoJ BioBlitz August 2018. 1002 records from Suivi des oiseaux de passage : programme ACT - Programme ACT : Répartition Pie bavarde 2005 - 2009 Coordonnées GPS Lambert 93. 1627 records from JRS Wetands data Rwanda, 2019. 82 records from Plan de gestion 2019 - 2023 de la station botanique du Normandin (33) mené par le CEN Nouvelle-Aquitaine - Observations faunistiques (inventaire) réalisées par le CEN Aquitaine. 582 records from Microplankton abundance at Station MARCH-1998-GN36199804611MNB03 in the euphotic zone of the Aegean Sea in March 1998. Part 2 - dinoflagellates. 16257 records from SILENE-FAUNE-PACA - Muséum_de_Toulon_et_du_Var_2017_12_18. 29412 records from EDP Baixo Sabor: Bat Roosts - Ecological Monitoring Program (PME) (2008-2014). 11 records from Plan de gestion 2013 - 2017 du site de la Butte de la Lot (33) mené par le CEN Aquitaine - Observations faunistiques fortuites réalisées par le CEN Aquitaine. 1689 records from Inventario de macroalgas de Isla Guadalupe, México. 308 records from Protocole de recensement des collisions entre la faune sauvage et les véhicules du département des Pyrénées-Atlantiques - Données de mortalité de la faune par collision avec les véhicules sur le réseau routier du département des Pyrénées-Atlantiques - 2019- 2020. 2 records from Bibliographie de la faune, la flore et la fonge de France métropolitaine et outre-mer - Bolletino del Museo Civico di Storia Naturale di Verona, Botanica Zoologica [2000-]. 277 records from BD de la plateforme partagée pour la diffusion des données naturalistes de Haute-Normandie - Programme de valorisation des zones humides chassées - volet Oiseaux. 211 records from RD752 – CRENEAU A 2 X 2 VOIES ENTRE SAINT-PIERRE-MONTLIMART ET BEAUPREAU / COMMUNES DE MONTREVAULT-SUR-EVRE ET BEAUPREAU-EN-MAUGES - RD752 CD49 SAGE Juillet 2014 - aout 2015. 103 records from Rare species of animals and plants of the flood zone of the Oleksandrivka Reservoir of the Buzk's Gard National Nature Park. 53 records from Plan de gestion 2017 - 2021 du site des Landes humides de Mazerolles (64) mené par le CEN Nouvelle-Aquitaine - Observations faunistiques (inventaire) réalisées par le CEN Nouvelle-Aquitaine. 272 records from BIRDRACE Niederlausitz-Team. 535 records from Bibliographie de la faune, la flore et la fonge de France métropolitaine et outre-mer - L'Amateur de Papillons. 148 records from Schulgarten Huttenheim (Philippsburg/Baden). 502 records from AMAPPS Southeast Aerial Cruise Spring 2014. 441 records from Línea base del medio biótico en los bosques dentro de la zona propuesta para Acuerdos de Conservación Voluntaria en la microcuenca de la Quebrada Aguazula - Rincón del Soldado_Yopal. 1292 records from Projet avidune - Etude de l'avifaune des dunes d'Aquitaine - Inventaire et suivi Avifaune. 2 records from Saisie de données naturalistes d'observateurs indépendants sur la plateforme de l'Observatoire FAUNA - Données naturalistes de Damien TROQUEREAU. 335 records from Poissons et Crustacés d'eau douce de la Martinique. 20 records from Happywhale - Sei Whale in South Pacific Ocean. 7657 records from British Antarctic (Terra Nova) Expedition, 1910-1913. 460 records from Marine Mammal Observation - Total Denmark 2013-2020. 7105 records from Invasive species - Chinese mitten crab (Eriocheir sinensis) in Flanders, Belgium. 364 records from Chronicle of Nature - Phenology of Birds of Ilmensky State Nature Reserve, Russian Academy of Sciences, Urals Branch. 306 records from Parc éolien de La Bussière - Données biodiversité. 1003 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de Laurent KREMMER. 240 records from Planktic foraminifera counts at CTD station PS55/083-1. 79 records from Grand Rhinolophe et trame verte bocagère en Poitou-Charentes - Données sur les colonies de reproduction et d'hivernages des chiroptères de Charente-Maritime. 1716 records from The Environmental Sample Collection of Spiders at the Staatliches Museum für Naturkunde Karlsruhe. 146 records from Steinbruch Mainz-Weisenau. 1140 records from Total foraminifera counts of multinet M12/3_MSN557. 2619 records from Fauna y flora del municipio de Lipa, Arauca. 24439 records from Weevil and Bark Beetle records via iRecord. 95 records from Macroalgas del atolón Albuquerque durante la Expedición Seaflower 2018 - Proyecto Colombia BIO. 912 records from Plasm bearing foraminifera counts from multinet SO119_MSN1285. 38 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Corvidae. 14674 records from Données du Réseau d'observateurs des mammifères marins en mer de la Manche - Observations du Grand dauphin du Golfe normand-breton. 320 records from Caracterización hidrogeológica para el diagnóstico ambiental de alternativas del proyecto hidroeléctrico San Bartolomé (ISAGEN y HMV).. 51 records from Chronicle of Nature - Phenology of Reptiles of Pechoro-Ilych State Nature Reserve. 16 records from Occurrence of recent nannoplankton in multi-net sample at M1_NET243, Arabian Sea (Fig. 2). 3759 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del Parque Natural Regional El Vinculo. 28 records from Nationalpark Harz Schul-AG Braunlage. 13450 records from Israeli Butterfly Monitoring Scheme (BMS-IL). 1 records from Observations naturalistes indépendantes d'origine privée partagées sur la base de données Kollect Nouvelle-Aquitaine - Observations faunistiques de Gérard LALANDE. 140 records from Inventaire de la faune aviaire et de l'Ichtyofaune de la mare de l'Abarkaizé et des Oiseaux de Dan Saga. 3636 records from Fish: Records for Kent.. 142 records from INVENTAIRES WEEK END DE LA BIODIVERSITE - Inventaires we biodiversité 2019. 239 records from Données transmises au PNR Périgord-Limousin n'étant pas commanditées par le parc - Inventaire Arachnides lors des rencontres de l'ASFRA en Dordogne. 38 records from Was lebt in der Brutzwiese?. 18003 records from Phytocenoteca of the laboratory of ecosystem theory (Plants). 15 records from Biodiversity Surveys, South-east Arnhem Land. 74 records from Phytoplankton abundance at station Sechin_2003-07-15_2, Casma, Peru. 94 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du/de la naturaliste Fourrier Thibault provenant de la base de donnée du SINP Île-de-France CETTIA. 636 records from Numérisation des données faune contenues dans les Bulletins de la Société Linnéenne de Bordeaux - Bulletin de la Société Linnéenne de Bordeaux, Tome 144 (N.S) n° 37 (2), 2009 - Données faune. 2793 records from Oiseaux des jardins - Inventaire indépendant de FrédérIc Revers. 1694 records from (Figure 3) Distribution of planktonic foraminifers in the Upper Cretaceous of DSDP Hole 71-511. 1054 records from Aves de la cuenca alta y media del río Bita, (Vichada) Colombia. 2273 records from Monitoreo de la población de la guacamaya verde en la Reserva de la Biosfera Tehuacán-Cuicatlán. 1998 records from (Table 1) Dinoflagellate range chart of ODP Hole 120-748C. 819 records from (Table 3) Occurrence of benthic foraminifers in ODP Hole 116-718C. 86 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de Pierre-Alexis RAULT. 68 records from The Fungal Collection at the Senckenberg Museum für Naturkunde Görlitz. 376028 records from USGS Patuxent Wildlife Research Center Seabirds Compendium. 28 records from Halophila stipulacea in the Caribbean Sea. 156 records from Levantamento da vegetação arbustiva do Parque Nacional do Jaú. 6 records from Programme « Papillons menacés des zones humides » en Aquitaine - Données de papillons collectées par le réserve naturelle géologique. 456 records from Phytoplankton abundance off Chao island in Juli 2003, Peru. 860 records from Taxa occurrences and composition of benthic macroinvertebrates from biodiversity surveys on Lake Victoria, Uganda (2001-2006). 295 records from Saisie de données naturalistes d'observateurs indépendants sur la plateforme de l'Observatoire FAUNA - Données naturalistes de Philippe LEGAY. 82 records from Numérisation des données faune contenues dans les Bulletins de la Société Linnéenne de Bordeaux - Bulletin de la Société Linnéenne de Bordeaux, Tome 148 (N.S) n° 41 (1), 2013 - Données faune. 1281 records from Etat des lieux des suivis effectués dans le cadre de la LGV SEA - Suivi Avifaune Lande sèches. 12 records from Plan de gestion Les Mattes de Paladon et Marais de Neyran - Suivi serpent. 26 records from Caracterización Ecológica de la Ornitofauna del Humedal Costero Obregón. 221 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Turdidae. 307 records from Chronicle of Nature - Phenology of Amphibia of Darwin Nature Biosphere Reserve. 2271 records from Happywhale - Humpback Whale in Indian Ocean. 28 records from Occurrence of mammalia relicts at site Bettelküche. 33318 records from BrioCAT: Banco de datos de los briòfitos de Cataluña. 804 records from Phytoplankton abundance in surface water in November 1997, Pisco, Peru. 266 records from Abundance of broken diatom frustules measured on water bottle samples at station PS58/049-3. 60071 records from TPWD HARC Texas Coastal Fisheries Matagorda Bay Trawl. 473 records from Projet éolien de Liniez II - Inventaires écologiques. 9 records from Happywhale - Northern Right Whale Dolphin in North Pacific Ocean. 347 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données de la structure Département 78 provenant de la base de donnée du SINP Île-de-France CETTIA. 150 records from Registros de Nerita fulgurans asociados a microplasticos en las playas de Santa Marta y Puebloviejo. 97 records from Plantación de árboles nativos con fines de restauración en el departamento de Cundinamarca, como parte de la iniciativa 180 millones de árboles nativos. 2326 records from DEMNA-DNE : Freshwater mussels occurrences in Wallonia. 2703 records from Abundance of algae in the Aral Sea. 22 records from Ahuyentamiento, rescate y reubicación de fauna en el área de influencia directa del proyecto Hidroeléctrico Mulatos II. 912 records from Plasm bearing foraminifera counts of multinet SO118_MSN1253. 29 records from Naturerfahrung. 509 records from Programmes d'Atlas de la biodiversité communale (ABC) - Atlas de la Biodiversité Communale sur les communes de Montmaurin, Lespugue et Blajan - Haute-Garonne - Données du CEN MP. 88 records from NMML Killer Whale Vessel, Alaska Peninsula 1993. 912 records from Total foraminifera counts from M35/1_MSN1047. 908 records from Bitunicate ascomycetes (Dothideomycetes and Chaetothyriomycetidae) on bark and wood of selected hosts in Norway. 953 records from Données naturalistes de Damien Combrisson. 3 records from Nano and microzooplankton abundance and biomass at station NBP96-04A-14-13. 65 records from Leben in und an der Ruwer sowie ihren Nebenbächen. 6652 records from Inventory of plant species through Benin (West Africa). 19 records from BD de la plateforme partagée pour la diffusion des données naturalistes de Haute-Normandie - Suivi des reptiles des landes du Technopôle du Madrillet. 47 records from Weide am Ostufer des Zotzensees, Müritz-Nationalpark. 684 records from Total foraminifera counts of multinet M12/3_MSN535. 896 records from Data on agroforestry plant species of Benin. 4465 records from Insectes Hyménoptères Formicidés de Corse. 1016 records from Suivi des oiseaux de passage : programme ACT - Programme ACT : Répartition Alouette des champs 2012 - 2016 Coordonnées GPS Lambert 93. 3882 records from National Trust for Scotland Mar Lodge Montane Scrub Surveys 2016-2018. 29 records from Mollusques continentaux de France - Données malacologiques du site Natura 2000 de Cessière-Montbavin. 1017 records from Suivi des oiseaux de passage : programme ACT - Programme ACT : Répartition Grive musicienne 2006 - 2010 Coordonnées GPS Lambert 93. 85 records from Observations naturalistes indépendantes d'origine privée partagées sur la base de données Kollect Nouvelle-Aquitaine - Observations faunistiques de Mikaël PAILLET. 912 records from Total foraminifera counts of multinet M21/5_MSN731. 912 records from Total foraminifera counts from multinet M31/2_MSN888. 66 records from Suivis faunistiques du site du Moulin de la Ville - Suivi Amphibien - POPAmphibien. 486 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du/de la naturaliste Hasrouni Sami provenant de la base de donnée du SINP Île-de-France CETTIA. 5621 records from Plan d'Aménagement participative de la Forêt Classée d'Alédjo (Togo). 31936 records from Records of Avifauna of Wetlands around Keoladeo National Park, Bharatpur, India. 2011 records from UNCW Right Whale Aerial Surveys 2008. 1 records from Données espèces - Expertise IQE 310. 579 records from New records of invasive mammals from the sub-Antarctic Cape Horn Archipelago (Neovison vison). 20588 records from FBIP:IZIKO-UCT:Historical Invertebrates (1930-1980). 564 records from Atewa Range Forest Reserve Bryophytes dataset, Ghana. 7 records from The publication of primary biological events in the international GBIF (Global Biodiversity Information Facility) network: A case study with a small dataset of field collected occurrence samples of Buriti palms (Mauritia flexuosa).. 857 records from Field Study Group of the Dutch Mammal Society (NL) - 2004 - Mammal Survey Rakitovec, Slovenia. 1296 records from Avifauna de los Parques Ecológicos Distritales de Montaña del Distrito Capital. 37 records from Naturbelassene ehemalige Wiese am Haselbach (Privates Schutzgebiet). 1014 records from Suivi des oiseaux de passage : programme ACT - Programme ACT : Répartition Pie bavarde 2006 - 2010 Coordonnées GPS Lambert 93. 1734 records from Phytoplankton abundance in surface water in October 1996, Ilo, Peru. 1954 records from CLICNAT- Base de données naturaliste picarde - Données de terrains coproduites par ADEP et CPIE Pays de l'Aisne. 6083 records from Sepsidae (Diptera) records from Britain and Ireland to 1985. 36 records from DUML coastal surveys on the occurrence, distribution and density of marine mammals in Camp Lejeune 2010-2013. 1022 records from Suivi des oiseaux de passage : programme ACT - Programme ACT : Répartition Grive musicienne 2000 - 2004 Coordonnées GPS Lambert 93. 3 records from Microzooplankton abundance and biomass at station NBP97-08-07-1. 1 records from Synthèse de la Répartition des populations de mouflon corse en 2011 (réseau Ongulés sauvages ONCFS-FNC-FDC). 64 records from Phytoplankton abundance at station Sechin_2003-08-27_2, Casma, Peru. 1 records from Saisie de données naturalistes d'observateurs indépendants sur la plateforme de l'Observatoire FAUNA - Données naturalistes de Camille GAUTIER. 79 records from Etude d'état initial de la biodiversité dans le cadre des EIES sur les plateaux situés dans la zone sud (Pompo) de la concession minière de Guinea Alumina Corporation(GAC) dans la region de Boké (CESP2016-022). 936 records from Alterra (NL) - Microarthropods inventory in Dune vegetation. 1 records from Occurrence of mammalia relicts at site High Furlong. 30 records from Site Condition Monitoring of dragonflies on Loch aí Mhuilinn NNR - 2002. 1480 records from Observations naturalistes indépendantes d'origine privée partagées sur la base de données Kollect Nouvelle-Aquitaine - Observations faunistiques de Pierre-Yves GOURVIL. 53 records from Occurrence of mammalia relicts at site la Grotte des Eglises. 67 records from Einen Tag lang Forscher sein - Die 5c der Erich-Kästner-Schule erforscht das Bachemer Wiesental. 3752 records from Inventaire et évaluation des pelouses calcicoles du Parc Naturel Régional du Marais Poitevin 2017-2018 - Inventaire des pelouses calcicoles du PNR du Marais Poitevin 2017. 17741 records from Chrysomelidae beetle data from iRecord. 943 records from Seasonal fluctuation of the meiobenthos community in Avicennia marina mangrove sediments at Gazi Bay (Kenya) between 1992 and 1993. 12 records from Plan de gestion 2019 - 2023 du site du coteau de Lembeye (64) mené par le CEN Aquitaine - Observations faunistiques fortuites réalisées par le CEN Nouvelle-Aquitaine. 1026 records from Inventaires complémentaires des espèces déterminantes ZNIEFF - Données naturalistes sur des périmètres pour créations de nouvelles ZNIEFF ou atualisation de ZNIEFF existantes. 860 records from Registros biológicos asociados al monitoreo de la diversidad de escarabajos en paisajes ganaderos silvopastoriles - Unillanos 2019. 999 records from Presence-absence of plant habitat specialists in 15 patches. 227 records from Data on cetacean strandings (1999 - 2014) on the Ukrainian coast of the Black Sea and the Sea of Azov and adjoining areas. 1022 records from Suivi des oiseaux de passage : programme ACT - Programme ACT : Répartition Pie bavarde 2009 - 2013 Coordonnées GPS Lambert 93. 1897 records from Registros Primates Neotropicales Convocatoria APC. 126 records from Mica - Muskrat, Raccoon and Coypu occurrences collected by ITAW in Germany. 232 records from Borstgrasrasen um die Burg Baldenau im Oberen Dhrontal. 1 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Fregatidae. 77 records from Incorporation of Mg and Sr in calcite of cultured benthic foraminifera (Heterostegina depressa and Ammonia tepida) and seawater carbonate chemistry, 2010. 202 records from Observations naturalistes indépendantes d'origine privée partagées sur la base de données Kollect Nouvelle-Aquitaine - Observations faunistiques de Jean HAXAIRE. 15571 records from Inventaire des Mollusques Sphaeriidae de France - Mollusques dulcicoles de France - Jacques MOUTHON. 50 records from Antractic whale observation on a platform of opportunity abroad krill fishing vessel "Dalmor II", April - July 2011.. 360 records from Planktic foraminifera counts at CTD station PS55/079-1. 69 records from Foraminifera species abundances from tow TT007_15-MOC23. 415 records from Animation des 4 sites Natura 2000 des zones humides du Marensin - Inventaire et suivi odonate/Fadet des laîches des sites Natura2000 ‘Zones humides de l’étang de Léon’ et ‘Zones humides de l’arrière dune du Marensin’. 36 records from Schulgelände Lise Meitner Realschule (Paderborn). 111 records from Birdrace-Uhulogen-Lippe. 17 records from Feral Pigs - Sightings and Cull records - 2018-2019. 5 records from Plan de gestion 2019 - 2023 du site des Grottes de Sare (64) mené par le CEN Nouvelle-Aquitaine - Observations faunistiques (inventaire) réalisées par le CEN Nouvelle-Aquitaine. 450 records from Projet de carrière de matériaux alluvionnaires - Les Orangers - Commune de Saint-Benoît - Flore. 2126 records from Computarización de la Colección de helmintos parásitos de peces del estado de Tabasco. 22 records from Stable carbon and oxygen isotope record of Cretaceous planktonic foraminifera from DSDP (Table 1). 136 records from Birdrace-SpeedBirder-Zwickauer_Land. 83 records from Birdrace-Die_Vogelscheuchen-Herford. 373 records from Otter survey of Ireland 2004 & 2005. 336169 records from Observatoire de la Biodiversité des Jardins (OBJ) - Données Observatoire des Papillons des Jardins. 20 records from Occurrence of mammalia relicts at site Tokod-Nagyberek. 2 records from Microplankton counts and carbon biomass at station TT007_9-CTD108. 1056 records from Deep-water azooxanthellate Scleractinia from Vanuatu, and Wallis and Futuna Islands. 6247 records from Census of medical plant species of Benin (West Africa) by SOS Biodiversity. 84 records from BIRDRACE Vogelscheuchen. 120 records from Phytoplankton abundance measured in surface water during Charles Darwin cruise CD85. 249 records from Données opportunistes produites par Alexandre RUFFONI dans le cadre de l’élaboration d’un guide de détermination des larves de plécoptères. 1556 records from Happywhale - Gray Whale in North Pacific Ocean. 81 records from Birdrace-Die_Ornithomaten-Herford. 133688 records from Suivi Temporel des Rhopalocères de France (STERF). 386 records from Poliquetos criptobentonicos en Orbicella annularis en arrecifes coralinos del PNA de Los Roques Venezuela. 1080 records from (Figure 4) Ranges of Cenozoic calcareous nannofossil species observed at DSDP Hole 77-536. 917 records from Monitoreo de aves por medio de puntos de conteo en el Santuario de Flora y Fauna Galeras en 2018. 84981 records from NINA Vanndata fisk. 103 records from Mammals (UWEP-MM). 2485 records from Study of epifauna and meiobenthos by means of cage experiments in a Ceriops tagal and Avicennia marina mangrove at Gazi Bay (Kenya) in August and September 1992. 1140 records from Total foraminifera counts of multinet POS247/2_MSN1386. 510 records from BD de la plateforme partagée pour la diffusion des données naturalistes de Haute-Normandie - Inventaires des cygnes du département de l'Eure. 940 records from SeaTurtle surveys on Braamspunt by Green Heritage Fund of Suriname. 1321 records from Projet BiodiverCité - Données protocolées Odonates. 1960 records from Land-based observations of cetaceans in the waters of Beringa Island in 2007-2009. 349 records from PROJET EN FAVEUR DES HIRONDELLES 2018. 78 records from Liaison autoroutière concédée entre Machilly et Thonon les Bains et suppression des passages à niveau N° 65 et 66 à Perrignier Haute-Savoie - Amphibiens - Inventaire non standardisé - FRAPNA74 - 24HNAT. 4730 records from Phytoplankton abundance in the Wadden Sea off List, Sylt, North Sea in 2008. 1 records from Occurrence of mammalia relicts at site Ejstrup. 21526 records from Plan de vertebrados de la Patagonia. 92 records from Birdrace_TerraCamper-Münster. 21 records from Murciélagos de la isla de Providencia. Expedición Seaflower 2019 proyecto Colombia BIO. 1270 records from AlgaTerra. 6 records from Numérisation des données faune contenues dans les Bulletins de la Société Linnéenne de Bordeaux - Bulletin de la Société Linnéenne de Bordeaux, Tome 137 (N.S) n° 30 (1), 2002 - Données faune. 2 records from Occurrence of mammalia relicts at site Igstadt I. 308545 records from Activité générale du bureau d'étude BIOTOPE (1994 - 2013) - Données acquises dans le cadre de l'activité du bureau d'étude BIOTOPE (1994 - 2013). 199 records from Distribution of Aphrocallistes beatrix in the N. Atlantic. 864 records from Danielsberg (Mölltal, Kärnten). 255 records from Parc éolien des Portes de la Brenne - Données-SINP-Flore. 52 records from Citas de castor en el País Vasco - Sistema de Información de la Naturaleza de Euskadi. 95 records from Vegetación vascular terrestre, entomofauna y macrofauna de la Isla Cayo Serrana durante la Expedición Seaflower 2016 - Proyecto Colombia BIO. 13000 records from SILENE-FAUNE-PACA - LPO_PACA_2017_12_18. 47 records from Abundance and community structure of birds breeding in Kalahari woodland used as rangeland. 95 records from Projet de parc éolien de la Croix Guingal, sur la commune de Derval (44 590) - Flore - Croix Guingal 2014. 30 records from Jasus caverum (Crustacea: Decapoda: Palinuridae) from the eastern South Pacific Ocean. 34 records from Borkhart. 4233 records from (Table 4) Distribution of benthic foraminifera in ODP Site 120-750. 11463 records from Liste des pays par taxon spécimen TOGO. 1017 records from Suivi des oiseaux de passage : programme ACT - Programme ACT : Répartition Merle noir 2006 - 2010 Coordonnées GPS Lambert 93. 1022 records from Suivi des oiseaux de passage : programme ACT - Programme ACT : Répartition Faisan commun 2009 - 2013 Coordonnées GPS Lambert 93. 2073 records from NRW Regional Data: all taxa (sensitive species only), West Wales. 1704 records from 成龍溼地魚類生態紀錄. 238 records from List of Macroinvertebrate Species recorded in Vava’u during BioRAP survey. 64 records from (Table 4) Abundance distribution of the 'clavate' subspecies of the genus Globigerinelloides and Pseudoschackoina saundersi in the upper part of the Calabianca section. 245 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Informatisation des carnets de terrain de Georges Catherine. 352 records from (Table 4) Relative abundance of some planktonic foraminifera and fragmentation ratios for ODP Hole 117-728A samples. 566 records from Mariposas del País Vasco - Sistema de Información de la Naturaleza de Euskadi. 356 records from Bibliographie de la faune, la flore et la fonge de France métropolitaine et outre-mer - Rutilans. 18 records from Fauna Species of Camiguin Island, Philippines. 63 records from Fauna acuática asociada al Humedal Costero Obregón, Guapi, Cauca - 2013. 40 records from Sightings for Airborne Mine Neutralization System Aerial Monitoring in the NSWC PCD Study Area from October 2011, 2012. 76 records from SNH Invertebrate Site Condition Monitoring 2015: Lurgie Loch SSSI. 16 records from Benthic hard-bottom communities abundance at X-Huinay, Comau Fjord, Chile, in 2010. 1269 records from Microplankton abundance in the euphotic zone of the Aegean Sea in October-November 1991. 661 records from Données espèces Expertise IQE 311. 60 records from Fish species observations from a monitoring survey of two Lake Victoria affluent rivers (Rivers Kagera and Sio). 2550 records from Nematode genera abundance from Portuguese canyons HERMES HERMIONE. 192 records from (Table 4) Distribution of calcareous nannoplankton in selected samples of ODP Hole 112-681A. 912 records from Plasm bearing foraminifera counts of multinet M21/5_MSN734. 11 records from Elaboration entre 2017 et 2018 par le CEN Aquitaine du plan de gestion compensatoire de la centrale solaire de Saint-Avit (40) - Observations faunistiques (inventaire) réalisées par le CEN Aquitaine. 15130 records from MMS Surveys, SCB 1995-1997. 36 records from SILENE-FAUNE-PACA - BIOMEO_2017_12_18. 75548 records from India Biodiversity Portal publication grade dataset. 7125 records from Phytoplankton abundance during ARGOS cruise Argos90/8. 59 records from Inventaires sur le réseau Aquitaine Nature du PNR Périgord-Limousin - Inventaire sur le site de la Pierre levée. 27 records from (Table 2) Distribution of early late Eocene fossil content in ODP Hole 115-714A. 518 records from Fishes in MZNA-VERT: monitoring program in the Suspiro stream (Spain). 981 records from GOALS Vessel Surveys June - July 2013. 755532 records from Oiseaux de France métropolitaine en hiver 1977-1981. 16773 records from CLICNAT- Base de données naturaliste picarde - Données bibliographiques. 332 records from 6. Tag der Artenvielfalt Hockenheim Thema: Wald 12.-14.6.2009. 18 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT011_10-CTD121. 20815 records from Waterbird counts, Luomus dataset. 2 records from Microplankton counts and carbon biomass at station TT011_3-CTD33. 22 records from Inventaires et suivis sites "Espaces Naturels Sensibles" gérés par le Conseil Départemental des Landes - Inventaire "Espaces Naturels Sensibles" des saligues, (BORDÈRES-CAZÈRES-RENUNG). 235 records from Plan de gestion 2014 - 2018 de la Réserve Naturelle Régionale des carrières de Tercis-les-Bains (40) mené par le CEN Aquitaine - Observations faunistiques (inventaire) réalisées par le CEN Aquitaine. 38 records from (Table 1c) Principal petrographic characteristics and K-Ar isotope-geochronological data on samples from the finishing of the Late Neopleistocene activity phase of the Keli Volcanic Highland. 244 records from Etat des lieux des suivis effectués dans le cadre de la LGV SEA - Suivi Oiseaux de la commune de Sainte-Soline. 182 records from Polychaete Study in Northeastern Mediterranean Coast of Egypt. 10 records from SNH Invertebrate Site Condition Monitoring of Beetle Assemblage Features 2015: Taynish Woods SSSI. 281 records from ferme solaire de Marcoussis - données fauneflore. 70 records from Abundance of zooplankton in the Aral Sea. 31 records from Plan de gestion 2005 - 2009 du site du Coteau de Casserouge (47) mené par le CEN Aquitaine - Observations faunistiques (inventaire) réalisées par le CEN Aquitaine. 607 records from King penguin census data, Gadget Gully, Macquarie Island (1993-2008). 88 records from Noosa Shire Nature Map. 103 records from Biotop Binsenwiesen und Ernst-Reiter-Wiese (Wehrheim/Taunus). 2592 records from Phytoplankton abundance in surface water during cruise CD61. 228 records from Total foraminifera counts of trap L3_92_45. 42 records from "Schlechteberg" Ebersbach/Sa.. 2004 records from Inventaire des longicornes des Antilles - Inventaire des Coléoptères Longicornes des Antilles françaises. 1017 records from Suivi des oiseaux de passage : programme ACT - Programme ACT : Répartition Pie bavarde 2007 - 2011 Coordonnées GPS Lambert 93. 1360095 records from Estonian Naturalists’ Society. 2573315 records from Suffolk Biodiversity Information Service (SBIS) Dataset. 58 records from Numérisation des données faune contenues dans les Bulletins de la Société Linnéenne de Bordeaux - Bulletin de la Société Linnéenne de Bordeaux, Tome 137 (N.S) n° 30 (4), 2002 - Données faune. 1140 records from Plasm bearing foraminifera counts of multinet POS247/2_MSN1371. 32 records from Sideritis syriaca subsp. nusairiensis and Thymus sipyleus in Mount Lebanon. 163 records from Ptéridophytes de Martinique (forêts sempervirentes) - Les aires de plus grand intérêt patrimonial pour les ptéridophytes dans l'étage des forêts sempervirentes saisonnières tropicales à la Martinique. 105 records from Données rhopalocères 2014/2015 des Mattes de Paladon. 960 records from SILENE-FAUNE-PACA - Département_du_Var_2017_12_18. 8 records from Microzooplankton abundance and biomass at station TT054_7-18. 912 records from Total foraminifera counts of trap L2_92_A42. 7 records from Occurrence of mammalia relicts at site Salzgitter-Lebenstedt. 45 records from Plan de gestion 2007 - 2011 du site du Coteau de Peyroutet (47) mené par le CEN Aquitaine - Observations faunistiques (inventaire) réalisées par le CEN Aquitaine. 20 records from Schulgarten Waldorfschule Hassfurt. 1124 records from Seabird observations on the RV Falkor, Voyage FK210206, Coral Sea, Australia (2021). 69 records from MIRC NAVFAC Incidental Sightings - Vessel 1965-2014. 17 records from Projet de parc éolien en mer des îles d'Yeu et de Noirmoutier - demande de dérogation espèces protégées - Mammifères marins PT - Inventaire non protocolé. 127 records from Wildlife Observations Bardon Hill 31.5.09. 135 records from http://www.geo-artenvielfalt.de (www.geo-artenvielfalt.de) - Birdrace-Pody&Co.-Plön. 53 records from Phenological Center - Mushrooms (Laplandskiy). 4961 records from (Appendix II) Planktonic foraminiferal biostratigraphy of ODP Site 113-690. 35 records from Projet de parc solaire Figanieres - Oiseaux - inventaire non protocolé. 95 records from Inventaire en continu de la ZNIEFF 'Forêt du Verdus' - 720012953 - Observations faunistiques (inventaire) réalisées par le CEN Nouvelle-Aquitaine. 3997 records from Locations of seals in Patagonian Large Marine Ecosystem (OBIS South America, AR-OBIS, Sub-node). 260 records from Phytoplankton abundance during Arne Tiselius cruise AT91/2. 4203 records from SPC CoFish Fish Observations Federated States of Micronesia 2006. 13 records from Caracterización de Mamíferos en el área de Farallones, jurisdicción de CORPOGUAVIO. 55 records from SNH Invertebrate Site Condition Monitoring 2015: Rinns of Islay SSSI. 33419 records from WADFW PSAMP W1993. 19 records from Happywhale - White-beaked Dolphin in Arctic Ocean. 1 records from Données naturalistes de REYJOL Yorick. 2 records from Registros de almeja (Polymesoda arctata) en la Ciénaga de pajarales. 12 records from A first checklist of the Pteridophytes of Togo (West Africa). 111 records from University of Algarve and ICNB Cetacean Sightings 1999. 63 records from Réseau Loup - Lynx ONCFS - Lynx 2009 présence Régulière Mailles 10km Réseau Loup-Lynx ONCFS. 687 records from Bibliographie de la faune, la flore et la fonge de France métropolitaine et outre-mer - Annales de la Société entomologique de France [1832- ]. 164 records from Phytoplankton abundance at station Rigel_3_2005-07 in July 2005, Chipana, Chile. 83 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de DELATTRE Adrien. 3428 records from Macroinvertebrados y perifiton pertenecientes a cuatro regiones de Colombia. 728810 records from Kastikka Literature Sources. 7 records from Plan de gestion 2012 - 2016 du site des tourbières de Mées (40) mené par le CEN Aquitaine - Observations faunistiques (inventaire) réalisées par le CEN Aquitaine. 180 records from (Table 7) Distribution of the large, many-chambered Globigerinelloides species in DSDP Hole 79-545. 911 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du/de la naturaliste MOULIN Nicolas provenant de la base de donnée du SINP Île-de-France CETTIA. 912 records from Plasm bearing foraminifera counts of multinet M42/3_MSN1370. 60713 records from Belgian Coccinellidae - Ladybird beetles in Belgium. 14560 records from Larval fish at time series station Helgoland Roads, North Sea, in 2004. 404 records from Numérisation des données faune contenues dans les Bulletins de la Société Linnéenne de Bordeaux - Bulletin de la Société Linnéenne de Bordeaux, Tome 136 (N.S) n° 29 (1), 2001 - Données faune. 32784 records from Survey and monitoring records for Scottish Wildlife Trust reserves from reserve convenors and Trust volunteers - Verified data. 1140 records from Plasm bearing foraminifera counts from M35/1_MSN1067. 91 records from Kochertgraben II. 633 records from Records of otters from Site Condition Monitoring in Scotland 2011-2012. 2 records from Microplankton counts and carbon biomass at station TT011_4-CTD46. 99 records from Programme LIFE CROAA - Eradication de la Grenouille taureau : Tir des individus. 232 records from Elaboration du DOCOB du site Natura 2000 ‘Haute Cize’ (FR7212015) - Inventaire avifaune. 40071950 records from iNaturalist Research-grade Observations. 143 records from (Table 2) Dinocyst specimens per slide and relatice abundances in each sample of ODP Hole 120-748C. 566 records from SEFSC GoMMAPPS 2018 Fall Aerial Survey. 8609 records from Abundances and biological traits of the juveniles salmon sampled in the survey of Salmon abundance Indices in the Nivelle river (France). 277 records from Aunar esfuerzos y recursos técnicos, económicos y humanos con el fin de adelantar acciones de investigación para estimar las poblaciones y monitorear en el tiempo la rana venenosa Oophaga lehmanni en la localidad La Cascada (Valle del Cauca). 49 records from Cuxhaven Schlosspark, Klasse 5e- Amandus-Abendroth-Gymnasium. 120 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données de LACOSTE Frédéric (SAPROX). 1758 records from DBRC Reptile Records 1950 - 2015. 16522 records from Inventaire des Mammifères de France - Inventaire des Mammifères marins de France (métropole et outre-mer). 4 records from Bohemannia auriciliella (Nepticulidae) specimen data. 1365 records from (Figure 10) Range chart of selected dinocysts and acritarchs of ODP Hole 104-644B. 1 records from Appalachian State University, I. W. Carpenter, Jr. Herbarium. 7 records from Abundance and carbon biomass of phytoplankton at station TT007_3-CTD30. 44 records from Données du Parc National de la Guadeloupe - Données Racoon sur le territoire de la Guadeloupe. 187 records from Anfibios y Reptiles asociados a tres ventanas de la Orinoquia Colombiana - SULU I. 64 records from Réseau Loup - Lynx ONCFS - Lynx 1996 présence Occasionnelle Mailles 10km Réseau Loup-Lynx ONCFS. 70263 records from Digital Aerial Baseline Survey of Marine Wildlife in Support of Offshore Wind Energy - OPA 2018. 228 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du naturaliste DUFRENE ERIC provenant de la base de donnée du SINP Île-de-France CETTIA. 74 records from Numérisation des données faune contenues dans les Bulletins de la Société Linnéenne de Bordeaux - Bulletin de la Société Linnéenne de Bordeaux, Tome 149 (N.S) n° 43 (1), 2015 - Données faune. 7027 records from Visual sightings from Song of the Whale 1993-2013. 2 records from Happywhale - Short-beaked Common Dolphin in South Pacific Ocean. 36 records from Mittelriede Höhe Gliesmarode-Braunschweig. 24 records from Phytoplankton abundance in surface water in 2004, Ancon, Peru. 1197 records from Outer Hebrides Insect Records from Literature. 4159 records from DBG Mirabilis rotundifolia Demographic Monitoring. 17 records from Comunidad de Herpetos presentes en el río Tutunendo, Municipio de Quibdó-Chocó. 208 records from Stadt Königs Wusterhausen. 217 records from Atlas communaux de la Biodiversité du Parc Naturel Régional des Landes de Gascogne (PNRLG) - Inventaire des odonates 2014. 1471 records from NMML 2002-2010 Bering Sea Shelf Cetacean Survey. 2 records from Microzooplankton abundance and biomass at station TT050_25-4. 374 records from Coastal and Marine Species Database. 900 records from Convention Fédération française de golf - MNHN 2016-2019. 151 records from Tasmanian Museum and Art Gallery provider for OZCAM. 1300 records from Data from vegetation plots at Atiquipa, Southern Peru. 54 records from Weidegebiete in der Selzrenaturierung. 123 records from Occurrence of mammalia relicts at site Veternica. 164 records from Marybio Foundation marine mammal shipboard sightings in Bahia San Antonio, Patagonia 2008-2010. 232 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du naturaliste DESCHATRE Thierry provenant de la base de donnée du SINP Île-de-France CETTIA. 1001 records from Mushroom (KIDR-MR). 22 records from Avifauna de los bosques húmedos y remanentes de Tierralta - Córdoba, 2011. 1401465 records from Données naturalistes opportunistes Faune-France - Liste des espèces de la faune sauvage de la base de données naturalistes Faune-France 2018.. 740 records from Monitoring data of marine turtles on the Togolese coast over 2012-2013 years. 587 records from Ciidae (Coleoptera) records from Britain and Ireland to 2004. 75 records from Bat diversity data by Formosan Golden Bat's Home. 1811 records from Point Count Data for TIDE's Private Land (Kern), Belize 2009-2013. 2365 records from Données issues de la bibliographie - Documents Mycologiques. 13 records from Liaison autoroutière concédée entre Machilly et Thonon les Bains et suppression des passages à niveau N° 65 et 66 à Perrignier Haute-Savoie - Mollusques - Inventaire non standardisé - FRAPNA74 - 24HNAT. 377 records from SILENE-FAUNE-PACA - CG04_2017_12_18. 1596 records from EDP Baixo Sabor: Construction and Reservoir Filling Phases – Wolf, (Canis lupus) Wild Boar (Sus scrofa) and Roe Deer (Capreolus capreolus) [camera-trapping] - [2011-2014]. 719 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du/de la naturaliste CUENIN Sibylle provenant de la base de donnée du SINP Île-de-France CETTIA. 589 records from Système d'Information sur la Nat
Keywords: GBIF; biodiversity; species occurrences